Transfer film, method for forming pattern, and method for manufacturing circuit wiring
By using a temporary support with low thermal deformation rate and a photosensitive layer in the transfer film, combined with a thermoplastic resin layer, the problem of substrate deformation is solved, and more stable bonding and pattern formation is achieved.
Patent Information
- Application Number
- CN202380043356.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-01-05
- Filing Date
- 2023-05-19
- Publication Date
- 2025-01-10
AI Technical Summary
During the use of the transfer film, the substrate is prone to deform due to thermal expansion and contraction, resulting in deformation problems when peeling off the temporary support after bonding.
A temporary support with a thermal deformation rate of less than 1.0%, and a photosensitive layer and an intermediate layer are added to the transfer film, including a thermoplastic resin layer, to control the surface contact between the transfer layer and the substrate and the surface roughness to ensure the transfer layer The water content and iron atom content are within a suitable range to reduce deformation of the substrate.
The deformation of the substrate is effectively suppressed, the bonding stability of the transfer film and the accuracy of pattern formation are improved, and the service life of the substrate is extended.
Smart Images

Figure CN119300974A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a transfer film, a method for forming a pattern and a method for manufacturing circuit wiring. Background Art
[0002] Since the number of steps for obtaining a predetermined pattern is small, a method of disposing a transfer layer on an arbitrary substrate using a transfer film, exposing the transfer layer through a mask, and then developing the transferred layer is widely used.
[0003] For example, International Publication No. 2017 / 007001 discloses a photosensitive element comprising a support film, an intermediate layer, and a photosensitive layer in this order, wherein the thickness of the support film is 20 μm or more, and the number of particles having a diameter of 5 μm or more contained in the support film is 30 particles / mm. 2 the following. Summary of the invention
[0004] Technical issues to be solved by the invention
[0005] In conventional transfer films, it is known that if the temporary support is peeled off after the transfer film and the substrate are bonded together, the substrate will be deformed. Therefore, it is required to suppress the deformation of the substrate.
[0006] According to one embodiment of the present invention, a transfer film capable of suppressing deformation of a substrate used in a transfer step can be provided.
[0007] Furthermore, according to another embodiment of the present invention, a method for forming a pattern and a method for manufacturing a circuit board using the transfer film can be provided.
[0008] Means for solving technical problems
[0009] The present invention includes the following aspects.
[0010] <1> A transfer film includes a temporary support and a transfer layer disposed on the temporary support, wherein the thermal deformation rate of the temporary support is 1.0% or less.
[0011] <2> according to <1> The transfer film, wherein
[0012] The surface free energy of the transfer layer on the side facing the temporary support is 68.0 mJ / m 2 the following.
[0013] <3> according to <1> or <2> The transfer film, wherein
[0014] The transfer layer is in contact with the surface of the temporary support, and the surface roughness Rmax of the transfer layer-side surface of the temporary support is 0.5 μm or less.
[0015] <4> according to <1> to <3> The transfer film as described in any one of the preceding claims, wherein
[0016] The transfer layer includes a photosensitive layer.
[0017] <5> according to <4> The transfer film, wherein
[0018] The transfer layer includes an intermediate layer between the temporary support and the photosensitive layer.
[0019] <6> according to <5> The transfer film, wherein
[0020] The transfer layer includes a thermoplastic resin layer between the temporary support and the intermediate layer.
[0021] <7> according to <1> to <6> The transfer film as described in any one of the preceding claims, wherein
[0022] The temporary support has a haze of greater than 2.0%.
[0023] <8> according to <1> to <7> The transfer film as described in any one of the preceding claims, wherein
[0024] The total number of particles with a diameter of 5 μm or more and aggregates with a diameter of 5 μm or more contained in the temporary support is more than 30 / mm 2 .
[0025] <9> according to <1> to <8> The transfer film as described in any one of the preceding claims, wherein
[0026] The temporary support body contains a 13.5mm 2 The area in which the total area ratio of the optical abnormal area during observation is greater than 300 ppm.
[0027] <10> according to <1> to <9> The transfer film as described in any one of the preceding claims, wherein
[0028] The thickness of the temporary support is 25 μm or more.
[0029] <11> according to <4> to <6> The transfer film as described in any one of the preceding claims, wherein
[0030] The photosensitive layer contains an alkali-soluble resin having an acid value of 80 mgKOH / g to 250 mgKOH / g.
[0031] <12> according to <4> to <6> The transfer film as described in any one of the preceding claims, wherein
[0032] The photosensitive layer contains an alkali-soluble resin having a crosslinkable group.
[0033] <13> according to <4> to <6> The transfer film as described in any one of the preceding claims, wherein
[0034] The photosensitive layer contains an alkali-soluble resin in which the mass ratio of the content of the structural unit derived from the (meth)acrylate to the total content of the structural unit derived from styrene and the structural unit derived from the styrene derivative is 0.3 to 2.5.
[0035] <14> according to <1> to <13> The transfer film as described in any one of the preceding claims, wherein
[0036] The content of water in the transfer layer is 0.1% by mass or more based on the total amount of the transfer layer.
[0037] <15> according to <4> to <6> The transfer film as described in any one of the preceding claims, wherein
[0038] The water content of the photosensitive layer is 0.1% by mass or more based on the total amount of the photosensitive layer.
[0039] <16> according to <1> to <14> The transfer film as described in any one of the preceding claims, wherein
[0040] The content of iron atoms in the transfer layer is 0.01 ppm to 10.0 ppm on a mass basis relative to the total amount of the transfer layer.
[0041] <17> according to <4> to <6> The transfer film as described in any one of the preceding claims, wherein
[0042] The content of iron atoms in the photosensitive layer is 0.01 ppm to 10.0 ppm on a mass basis relative to the total amount of the photosensitive layer.
[0043] <18> A method for forming a pattern, comprising the following steps: preparing a transfer film including a temporary support and a transfer layer arranged on the temporary support; bonding the transfer film and a substrate in a manner such that the surface of the transfer film on the side opposite to the surface of the temporary support contacts the substrate; peeling off the temporary support to obtain a laminate; exposing the laminate in a pattern; and developing the exposed laminate to form a pattern, wherein the thermal deformation rate of the temporary support is less than 1.0%.
[0044] <19> A method for manufacturing circuit wiring, comprising the following steps: preparing a transfer film including a temporary support and a transfer layer arranged on the temporary support; bonding the transfer film and a substrate in a manner such that the surface of the transfer film on the side opposite to the surface of the temporary support contacts the substrate; peeling off the temporary support to obtain a laminate; exposing the laminate in a pattern; developing the exposed laminate to form a pattern; plating an area of the substrate where the pattern is not arranged; and peeling off the pattern, wherein the thermal deformation rate of the temporary support is less than 1.0%.
[0045] Effects of the Invention
[0046] According to one embodiment of the present invention, a transfer film capable of suppressing deformation of a substrate used in a transfer step can be provided.
[0047] Furthermore, according to another embodiment of the present invention, a method for forming a pattern and a method for manufacturing a circuit board using the transfer film can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 This is a schematic diagram showing an example of the structure of the transfer film according to the present invention. DETAILED DESCRIPTION
[0049] Hereinafter, the present invention will be described in detail.
[0050] In the present invention, a numerical range expressed using "to" means a range including the numerical values described before and after "to" as the lower limit and the upper limit.
[0051] In the invention, in the numerical ranges recorded in stages, the upper limit or lower limit recorded in a certain numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In addition, in the numerical ranges recorded in this specification, the upper limit or lower limit recorded in a certain numerical range can also be replaced by the value shown in the embodiment.
[0052] In the present invention, each component may contain a plurality of corresponding substances.
[0053] In the present invention, the term "layer" includes not only a case where the layer or film is formed in the entire region when the region where the layer or film exists is observed, but also a case where the layer or film is formed in only a part of the region.
[0054] In the present invention, the term "process" includes not only an independent process but also a process that cannot be clearly distinguished from other processes as long as the intended purpose of the process can be achieved.
[0055] In the present invention, "transparent" means that the average transmittance of visible light with a wavelength of 400 nm to 700 nm is 80% or more, preferably 90% or more.
[0056] In the present invention, the transmittance is a value determined using spectrophotometry, and can be measured using, for example, a spectrophotometer U-3310 manufactured by Hitachi, Ltd.
[0057] In the present invention, unless otherwise specified, the weight average molecular weight (Mw) and the number average molecular weight (Mn) are values calculated in terms of polystyrene using a standard substance, measured using a gel permeation chromatography (GPC) analyzer using TSKgel GMHxL, TSKgel G4000HxL or TSKgel G2000HxL (all trade names manufactured by TOSOH CORPORATION) as a column, THF (tetrahydrofuran) as an eluent, a differential refractometer as a detector, and polystyrene as a standard substance.
[0058] In the present invention, unless otherwise specified, the ratio of the structural units of the polymer is a mass ratio.
[0059] In the present invention, unless otherwise specified, the molecular weight of a compound having a molecular weight distribution is a weight average molecular weight (Mw).
[0060] In the present invention, "(meth)acrylic acid" is a concept including both acrylic acid and methacrylic acid. "(meth)acryloyloxy" is a concept including both acryloxy and methacryloyloxy. "(Meth)acryloyl" is a concept including both acryloxy and methacryloyl.
[0061] In the present invention, "alkali-soluble" means that the solubility of sodium carbonate in 100 g of a mass % aqueous solution at 22°C is 0.1 g or more.
[0062] In the present invention, "water-soluble" means that the solubility in 100 g of water at pH 7.0 at a liquid temperature of 22° C. is 0.1 g or more. Therefore, for example, a water-soluble resin refers to a resin that satisfies the above-mentioned solubility condition.
[0063] In the present invention, the "solid content" of the composition refers to the components that form the composition layer formed using the composition, and when the composition contains a solvent (organic solvent, water, etc.), it refers to all components other than the solvent. In addition, if it is a component that forms the composition layer, the liquid component is also regarded as a solid component.
[0064] In the present invention, the "thickness" is calculated as an average value of five arbitrary points measured by cross-sectional observation of an object using a SEM (Scanning Electron Microscope).
[0065] [Transfer film]
[0066] The transfer film according to the present invention includes a temporary support and a transfer layer disposed on the temporary support, and the thermal deformation rate of the temporary support is 1.0% or less.
[0067] The present inventors have found that deformation of the substrate in the transfer step can be suppressed by setting the thermal deformation rate of the temporary support body bonded to the transfer film side of the substrate in the transfer step to 1.0% or less.
[0068] In the past, it is known that if the temporary support is peeled off after the transfer film is attached to the substrate, the substrate will deform. It is believed that this is because the transfer film is more likely to expand due to heat than the substrate, and the transfer film will be attached to the substrate in an expanded state. Then, when the temporary support is peeled off, the transfer layer shrinks. It is believed that the substrate is deformed as a result.
[0069] In contrast, when the transfer film of the present invention is used, since the thermal deformation rate of the temporary support is 1.0% or less, the transfer film is less likely to expand and contract due to heat, and deformation of the substrate bonded to the transfer film can be suppressed.
[0070] Hereinafter, the transfer film according to the present invention will be described in detail.
[0071] The transfer film according to the present invention includes a temporary support and a transfer layer disposed on the temporary support.
[0072] In the transfer film, the temporary support and the transfer layer may be directly laminated without or with another layer. In addition, another layer may be laminated on the surface of the transfer layer opposite to the surface facing the temporary support.
[0073] As other layers except the temporary support and the transfer layer, a protective film is mentioned, for example.
[0074] The protective film is preferably disposed on the surface of the transfer layer opposite to the surface facing the temporary support.
[0075] Furthermore, each layer may be a single layer or a plurality of layers.
[0076] An example of the form of the transfer film according to the present invention is shown below, but the present invention is not limited thereto.
[0077] (1) "Temporary support / transfer layer (photosensitive layer) / protective film"
[0078] (2) "Temporary support / transfer layer (intermediate layer / photosensitive layer) / protective film"
[0079] (3) "temporary support / transfer layer (thermoplastic resin layer / intermediate layer / photosensitive layer) / protective film"
[0080] In each of the above structures, the photosensitive layer may be either a negative photosensitive layer or a positive photosensitive layer, but is preferably a negative photosensitive layer. Furthermore, the photosensitive layer is also preferably a colored resin layer.
[0081] The transfer film according to the present invention is preferably used as a transfer film for etching photoresist.
[0082] In the transfer film, when the photosensitive layer further has other layers on the side opposite to the temporary support body, the total thickness of the other layers arranged on the side opposite to the temporary support body of the photosensitive layer is preferably 0.1% to 30%, more preferably 0.1% to 20% relative to the thickness of the photosensitive layer.
[0083] From the viewpoint of suppressing the generation of bubbles during the laminating step described later, the maximum width of the corrugations of the transfer film is preferably 300 μm or less, more preferably 200 μm or less, and further preferably 60 μm or less. In addition, the maximum width of the corrugations of the transfer film is preferably 0 μm or more, more preferably 0.1 μm or more, and further preferably 1 μm or more.
[0084] The maximum width of the corrugations of the transfer film is a value measured by the following procedure.
[0085] First, the transfer film is cut into a size of 20 cm long and 20 cm wide in a direction perpendicular to the main surface to produce a test sample. In addition, when the transfer film has a protective film, peel off the protective film. Then, on a smooth and horizontal platform, the above test sample is allowed to stand still in such a way that the surface of the temporary support body is opposite to the platform. After standing still, the surface of the test sample is scanned with a laser microscope (for example, VK-9700SP manufactured by KEYENCE CORPORATION) within a 10 cm square range in the center of the test sample to obtain a three-dimensional surface image, and the minimum concave height is subtracted from the maximum convex height observed in the obtained three-dimensional surface image. The above operation is performed on 10 test samples, and the arithmetic mean thereof is taken as the "maximum width of the corrugation of the transfer film".
[0086] Hereinafter, the transfer film according to the present invention will be described with reference to an example of a specific embodiment.
[0087] Figure 1 The transfer film 20 shown includes a temporary support 11 , a transfer layer 12 including a thermoplastic resin layer 13 , an intermediate layer 15 and a photosensitive layer 17 , and a protective film 19 in this order.
[0088] in addition, Figure 1 The transfer film 20 shown is in a form in which the protective film 19 is provided, but the protective film 19 may not be provided.
[0089] and, Figure 1 The transfer film 20 shown is in a form in which the thermoplastic resin layer 13 and the intermediate layer 15 are arranged, but the thermoplastic resin layer 13 or the intermediate layer 15 or both may not be arranged.
[0090] Hereinafter, each element constituting the transfer film according to the present invention will be described.
[0091] Temporary support
[0092] The transfer film according to the present invention includes a temporary support.
[0093] The temporary support is a peelable support that supports the transfer layer.
[0094] The temporary support may be a single layer or a laminated body in which two or more layers are laminated.
[0095] Examples of the temporary support include a laminate consisting only of a substrate; a laminate including a substrate and a particle-containing layer disposed on one surface of the substrate; and a laminate including a substrate and a particle-containing layer disposed on both surfaces of the substrate.
[0096] Examples of the substrate constituting the temporary support include glass, resin films, and paper. From the viewpoint of strength, flexibility, and light transmittance, the substrate constituting the temporary support is preferably a resin film.
[0097] Examples of the resin film include polyethylene terephthalate (PET) films, cellulose triacetate films, polystyrene films, and polycarbonate films. Among them, the resin film is preferably a PET film, and more preferably a biaxially stretched PET film.
[0098] When the particle-containing layer is disposed on one surface or both surfaces of the substrate, the particle-containing layer may be a single layer or may be two or more layers.
[0099] The particle-containing layer is formed, for example, by applying a composition for a particle-containing layer on a substrate and drying it. In addition, the particle-containing layer can also be configured by a coextrusion method when forming a resin film. The composition for a particle-containing layer preferably includes a binder polymer and particles. The type of binder polymer is not particularly limited, and can be appropriately selected according to the purpose. As the binder polymer, for example, acrylic resins, urethane resins, olefin resins, styrene-butadiene resins, ester resins, vinyl chloride resins and vinylidene chloride resins can be cited. When configuring the particle-containing layer by a coextrusion method, PET is preferably used as the binder polymer.
[0100] The particle-containing layer may contain one type of the binder polymer and the particles, respectively, or may contain two or more types.
[0101] The particles contained in the particle-containing layer are not particularly limited and can be appropriately selected according to the purpose. The content of the particles in the particle-containing layer can be appropriately adjusted according to the amount of particles added in the particle-containing layer composition. In this specification, the particles contained in the particle-containing layer are referred to as "added particles".
[0102] The added particles are particles distinguished from impurities accidentally mixed in the manufacturing process of the temporary support and particles formed in the manufacturing process of the temporary support. The added particles are preferably particles having a characteristic of not melting at 200°C.
[0103] In the temporary support, whether or not there are added particles can be determined by, for example, the following method: Since the shape and distribution of the added particles are generally uniform, they can be determined by observation with an optical microscope.
[0104] Examples of the added particles include inorganic particles and organic particles.
[0105] Examples of the inorganic particles include particles of inorganic oxides such as silicon oxide (silica), titanium oxide (titania), zirconium oxide (zirconia), magnesium oxide (magnesia), and aluminum oxide (alumina).
[0106] Examples of the organic particles include particles of polymers such as acrylic resins, polyesters, polyurethanes, polycarbonates, polyolefins, and polystyrenes.
[0107] When the temporary support has a particle-containing layer, the additional particles contained in the particle-containing layer are preferably particles of an inorganic oxide.
[0108] The average particle size of the added particles is not particularly limited, and is, for example, 0.1 μm to 10 μm. A slice having a thickness of 100 nm is cut out using an ultramicrotome, and the average particle size is measured using a TEM (transmission electron microscope).
[0109] In the transfer film of the present invention, the thermal deformation rate of the temporary support is 1.0% or less, preferably 0.5% or less. The lower limit of the thermal deformation rate is not particularly limited, but is preferably 0%. By setting the thermal deformation rate of the temporary support to 1.0% or less, deformation of the substrate bonded to the transfer film can be suppressed.
[0110] In the present invention, the thermal deformation rate is measured by the following method.
[0111] On the main surface of the temporary support, a direction parallel to one of two sets of sides facing each other is referred to as an A direction, and a direction perpendicular to the A direction is referred to as a B direction.
[0112] A test piece cut to a length of 30 mm in the A direction and 4 mm in the B direction and a test piece cut to a length of 30 mm in the B direction and 4 mm in the A direction were prepared.
[0113] The following measurements were performed using two test pieces.
[0114] As a measuring device, a thermal expansion coefficient measuring device (product name: "TMA450EM", manufactured by TA Instruments) was used.
[0115] The measurement conditions are as follows.
[0116] Measurement mode: Stretch mode
[0117] Distance between grippers: 16mm
[0118] Set load: from 0.05N to 0.48N at 6.00N / min.
[0119] Each test piece was heated from 25° C. to 100° C. at a heating rate of 20° C. / min, and the elongation of each test piece was measured five times, and the average value was calculated.
[0120] The larger average value of the elongation of the two test pieces was adopted as the thermal deformation rate.
[0121] Examples of a method for reducing the thermal deformation rate of the temporary support include a method of increasing the thickness of the temporary support and a method of increasing the amount of particles contained in the temporary support by incorporating particles into the temporary support.
[0122] In the transfer film according to the present invention, the haze of the temporary support is preferably larger than 2.0% from the viewpoint of suppressing deformation of a substrate bonded to the transfer film.
[0123] From the above viewpoints, the haze of the temporary support is more preferably 2.5% or more. The upper limit of the haze is not particularly limited, and is, for example, 10%.
[0124] When patterning is formed using the transfer film of the present invention, the temporary support is preferably peeled off before exposure after the transfer film and substrate are bonded together. If the temporary support is peeled off before exposure, there is no need to consider the influence of the high haze of the temporary support on the exposure.
[0125] In the present invention, the haze is measured using a haze meter in accordance with JIS K7136: 2000. As the haze meter, for example, a product name "NDH-2000" manufactured by NIPPON DENSHOKU INDUSTRIES CO., LTD. is used.
[0126] Furthermore, in the transfer film of the present invention, from the viewpoint of suppressing deformation of the substrate bonded to the transfer film, the total number of particles having a diameter of 5 μm or more and aggregates having a diameter of 5 μm or more contained in the temporary support is preferably more than 30 particles / mm. 2 .
[0127] From the above viewpoints, the total number of the particles and aggregates is more preferably 40 particles / mm. 2 The upper limit of the total number is not particularly limited, and is, for example, 50 pieces / mm 2 .
[0128] The particles and aggregates mentioned here refer to particles and aggregates having an area where a polarization difference from the surrounding area can be observed when observing the temporary support body with a polarizing microscope. Examples of particles and aggregates include carbides of resin formed in the manufacture of the substrate and catalysts used in the manufacture of the substrate. In addition, when the particle-containing layer as described above is provided, the added particles contained in the particle-containing layer also correspond to the above-mentioned particles.
[0129] In the present invention, the total number of particles and aggregates contained in the temporary support is measured by the following method.
[0130] First, observe the temporary support with a polarizing microscope (insert "U-POT" filter and "U-AN360" filter into the product name: "BX60" as a simple polarizing microscope, objective lens 10x, manufactured by Olympus Corporation), and identify the part where polarization disorder occurs as foreign matter (particles or agglomerates). Observe the identified foreign matter with an incident laser microscope (product name: "Confocal Laser Microscope VL2000D", manufactured by Lasertec). In addition, use an optical microscope (product name: "BX60", objective lens 100x, manufactured by Olympus Corporation) to measure the diameter of the foreign matter, and measure the observation area 1mm 2 The number of foreign matter with a diameter of 5 μm or more contained in the sample was measured. In addition, when the foreign matter contained voids, the diameter including the voids was measured. When the foreign matter was not round, the longest diameter was measured.
[0131] When the transfer film of the present invention is used to form a pattern, after the transfer film and the substrate are bonded together, the temporary support is preferably peeled off before exposure. If the temporary support is peeled off before exposure, there is no need to consider the effect of the temporary support on the exposure due to the large number of particles and aggregates contained in the temporary support.
[0132] Furthermore, in the transfer film of the present invention, from the viewpoint of suppressing deformation of the substrate bonded to the transfer film, the temporary support preferably includes a 2 The area in which the total area ratio of the optical abnormal area during observation is greater than 300 ppm.
[0133] From the above viewpoints, the total area ratio of the optical abnormal regions is more preferably 350 ppm or more. The upper limit of the total area ratio is not particularly limited, and is, for example, 500 ppm.
[0134] In the present invention, the area of the optical abnormal region refers to the area of the optical abnormal region observed in a region extending from the center position of the thickness of the temporary support to 2 μm on one side or the other side in the thickness direction.
[0135] In the present invention, the optical abnormal region refers to a region whose optical properties are different from the main region of the temporary support (the resin constituting the temporary support) (specifically, a region where the reflectivity or refractive index is different from the main region, or a region where optical phenomena such as scattering and diffraction are more strongly generated than the main region). When the temporary support contains particles, for example, the optical abnormal region may include both a light-shielding portion based on the particles and an optical abnormal region other than the particles (for example, an abnormal refractive index region having a refractive index different from that of the particles and the main region of the temporary support). Examples of optical abnormal regions are regions where the orientation and / or crystallinity are different from the main region of the temporary support, air regions, regions of gases other than air, and hollow regions where there is almost no gas.
[0136] In the present invention, the total area of the optical abnormal regions is measured by the following method.
[0137] Insert a polarizing filter (OLS4000-QWP) on the upper part of the objective lens of an epi-laser microscope (OLS-4100 manufactured by 0lympus). Next, use a porous adsorption plate (65F-HG manufactured by UNIVERSAL GIKEN CO., LTD.) and a vacuum pump to horizontally suck and fix a temporary support cut into 30mm×30mm on the platform of the laser microscope. Observe the sucked and fixed temporary support under the conditions of 50 times the objective lens and 60 laser light intensity (laser wavelength is 405nm). At this time, the area from the center position of the thickness of the temporary support to 2μm on one side or the other side in the thickness direction is defined as the measurement area, and the measurement area of 259μm×260μm is measured at 200 measurement locations. Therefore, the total measurement area becomes 0.259mm×0.26mm×200=13.5mm 2 .
[0138] The light amount difference between the pixel with the maximum light amount and the pixel with the minimum light amount in the measured image is divided into 4096 gray levels (the value of the maximum light amount is 4095 and the value of the minimum light amount is 0). A histogram is made to graph the light amount distribution of the pixels in the image (horizontal axis: gray level of light amount (minimum value 0, maximum value 4095), vertical axis: number of pixels). The gray level after adding 400 gray levels to the larger of the two base values of the produced histogram is used as the threshold, and the measured image is binarized. The area of the pixels with light amount greater than the threshold is totaled, and the total area is used as the total area of the optical abnormal area. The ratio of the total area of the optical abnormal area to the measured area is calculated.
[0139] From the viewpoint of suppressing deformation of the substrate bonded to the transfer film, the thickness of the temporary support is preferably 25 μm or more, more preferably 50 μm or more, and further preferably 75 μm or more. The upper limit of the thickness is not particularly limited, and is, for example, 200 μm.
[0140] From the viewpoint of improving the adhesion with the transfer layer, the temporary support may be subjected to surface treatment such as ultraviolet irradiation, corona discharge, plasma treatment, etc. on the surface in contact with the transfer layer. When the surface treatment is performed by ultraviolet irradiation, the exposure amount is preferably 10 mJ / cm 2 ~2000mJ / cm 2 , more preferably 50mH / cm 2 ~1000mmJ / cm 2 .
[0141] As the light source for ultraviolet irradiation, for example, there can be mentioned light sources that emit light in the wavelength band of 150 nm to 450 nm (for example, low-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, carbon arc lamps, metal halide lamps, xenon lamps, chemical lamps, electrodeless discharge lamps, and light-emitting diodes (LEDs)). The output and illumination are not particularly limited.
[0142] The transfer layer is preferably in contact with the surface of the temporary support. From the viewpoint of transferring the unevenness of the temporary support to the transfer layer, the surface roughness Rmax of the transfer layer side surface of the temporary support is preferably 0.5 μm or less, more preferably 0.01 μm to 0.5 μm.
[0143] The surface roughness Rmax of the transfer layer side surface of the temporary support was measured by the following method.
[0144] In the present invention, the surface roughness Rmax is measured using a three-dimensional optical profiler (New View 7300, manufactured by Zygo Corporation).
[0145] First, peel off the temporary support from the transfer film. Obtain the surface profile of the transfer layer side surface of the temporary support. As the measurement / analysis software, use the Microscope Application of MetroPro ver8.3.2. Next, use the measurement / analysis software to display the Surface Map screen, and obtain the histogram data in the Surface Map screen. Obtain the surface roughness Rmax from the obtained histogram data. In addition, the surface roughness Rmax corresponds to the maximum height of the roughness curve under the reference length.
[0146] The temporary support may also be a recyclable product. As a recyclable product, a product obtained by washing a used film, shredding it, and using the shredded film as a raw material to form a film. As a specific example of a recyclable product, the Ecouse series of TORAY INDUSTRIES, INC. may be cited.
[0147] 〔Transfer layer〕
[0148] The transfer film according to the present invention includes a transfer layer.
[0149] From the viewpoint of easy peeling of the temporary support, the surface free energy of the transfer layer on the side facing the temporary support is preferably 68.0 mJ / m 2 Below, more preferably 50.0 mJ / cm 2 ~68.0mJ / cm 2 , more preferably 55.0 mJ / cm 2 ~65.OmJ / cm 2 .
[0150] In the present invention, the surface free energy (unit: mJ / m 2 ).
[0151] On the measurement surface of the transfer layer, 12 μL of pure water and diiodomethane were dripped at room temperature of 25°C and relative humidity of 50%. After 20 seconds, the contact angles were measured at three points using a contact angle meter CA-A (manufactured by Kyowa Interface Science Co., Ltd.), and the average value was taken as the contact angle. The contact angles of the two liquids obtained were used to calculate the dispersion force γ by the geometric mean method based on Owens-Wendt. d , polar force γ p and the surface energy γ (=γ d +γ p ).
[0152] The specific calculation method is shown below. The meaning of each symbol is as follows. SL When is the tension at the interface between a solid and a liquid, the following equation (1) holds true.
[0153] γ SL : Surface free energy of the membrane surface and the known liquid
[0154] γ S : Surface free energy of the membrane surface
[0155] γ L : The surface free energy of a known liquid
[0156] γ S d : Dispersion force component of the surface free energy of the membrane surface
[0157] γ S p : Polar force component of the surface free energy of the membrane surface
[0158] γ L d : Dispersion force component of the surface free energy of a known liquid
[0159] γ L p : The polar force component of the surface free energy of a known liquid
[0160] γ SL =γ S +γ L -2(γ S d γ L d ) 1 / 2 -2(γ S p γ L p ) 1 / 2 Formula (1)
[0161] The state when a smooth solid surface contacts a liquid droplet at a contact angle (θ) is expressed by the following equation (Young's equation).
[0162] γ S =γ SL +γ L cosθ···Formula (2)
[0163] When these equations (1) and (2) are combined, the following equation is obtained.
[0164] (γ s d γ Ld ) 1 / 2 +(γ s p γ L p ) 1 / 2 (=γ L (1+cosθ) / 2···Formula (3)
[0165] In fact, the contact angle (θ) of pure water and diiodomethane, the surface energy γ of the known liquids, L And each component (γ L d , γ L p ) into equation (3) to solve the simultaneous equations.
[0166] As a result, the surface free energy (γ S ).
[0167] The method for adjusting the surface free energy of the transfer layer on the side facing the temporary support to be within the above range is not particularly limited, and an example includes a method of providing an intermediate layer containing a water-soluble resin on the side in contact with the temporary support.
[0168] The transfer layer preferably contains water at least 0.1 mass %, more preferably at least 0.15 mass %, and even more preferably at least 0.3 mass % relative to the total amount of the transfer layer from the viewpoint of improving the sensitivity of the photosensitive layer. The upper limit of the water content is not particularly limited, and is, for example, 1.0 mass %.
[0169] The water content in the transfer layer can be adjusted by the drying method when forming the transfer layer.
[0170] In the present invention, the water content in the transfer layer is measured by the following method.
[0171] The transfer film was cut into small pieces of 5 mm × 30 mm in size as a sample, and the sample was inserted into the primary trapping tube (PAT) and covered with a lid. In addition, when a protective film is provided, a small piece of the peeled protective film is used as a sample and inserted immediately after peeling. The sample preparation was carried out at 23°C and 45% RH. A thermal desorption device (product name: "JTD-505III", manufactured by Japan Analytical Industry Co., Ltd.) was used to heat the mixture and measure the degassing to measure the water content.
[0172] If the developability is good, residues are less likely to remain on the pattern, and if the adhesion to the substrate is good, a finer pattern can be formed. From the viewpoint of improving the developability and the adhesion to the substrate, the content of iron atoms in the transfer layer is preferably 0.01 ppm to 10.0 ppm, more preferably 0.1 ppm to 10 ppm, and further preferably 0.2 ppm to 10 ppm based on the mass of the total amount of the transfer layer.
[0173] The iron content in the transfer layer can be adjusted by the composition of the photosensitive composition.
[0174] In the present invention, the content of iron atoms in the transfer layer is measured by the following method.
[0175] The content of iron atoms is measured by inductively coupled plasma (ICP) emission spectrometry described in JIS K1200-6. As a measuring apparatus, for example, an inductively coupled plasma mass spectrometer (ICP-MS): ICPMS-2030 (manufactured by Shimadzu Corporation) is used.
[0176] First, weigh 1.000 g of the transfer layer from the transfer film and use an electric furnace to ashed the transfer layer. Add 5 mL of nitric acid aqueous solution (manufactured by FUJIFILM Wako Pure Chemical Corporation; an aqueous solution obtained by mixing special grade nitric acid and ultrapure water in a ratio of 1:1) to the platinum crucible taken out of the electric furnace to dissolve the above-mentioned ashed product. Then, add 15 ml of ultrapure water to obtain an aqueous solution of the ashed product. The obtained aqueous solution is measured using the inductively coupled plasma (ICP) emission spectrometry method described in JIS K1200-6 to calculate the content of iron atoms in the transfer layer.
[0177] The transfer layer preferably includes a photosensitive layer in order to form a pattern.
[0178] <<Photosensitive layer>>
[0179] In a display device (organic electroluminescent (FL) display device and liquid crystal display device, etc.) having a touch panel such as an electrostatic capacitive input device, a conductive layer pattern such as an electrode pattern of a sensor corresponding to a visual recognition portion, a peripheral wiring portion, and wiring of a lead wiring portion is provided inside the touch panel. The following method is generally widely used to form a patterned layer: a negative photosensitive layer is provided on a substrate using a transfer film, etc., and the photosensitive layer is exposed through a mask having a desired pattern and then developed.
[0180] The photosensitive layer is preferably a negative photosensitive layer in which the solubility of the exposed portion to the developer is reduced by exposure and the non-exposed portion is removed by development. However, the photosensitive layer is not limited to a negative photosensitive layer, and may be a positive photosensitive layer in which the solubility of the exposed portion to the developer is increased by exposure and the exposed portion is removed by development.
[0181] The photosensitive layer is obtained by, for example, applying a photosensitive composition and drying it.
[0182] When the photosensitive layer is a negative photosensitive layer, the photosensitive layer preferably contains a resin, a polymerizable compound, and a polymerization initiator. Furthermore, when the photosensitive layer is a negative photosensitive layer, as described later, it is also preferred to contain an alkali-soluble resin (polymer A as an alkali-soluble resin, etc.) as part or all of the resin. That is, in one embodiment, the photosensitive layer preferably contains a resin containing an alkali-soluble resin, a polymerizable compound, and a polymerization initiator.
[0183] Such a photosensitive layer (negative photosensitive layer) preferably contains 10 to 90% by mass of a resin, 5 to 70% by mass of a polymerizable compound, and 0.01 to 20% by mass of a polymerization initiator based on the total mass of the photosensitive layer.
[0184] Hereinafter, each component will be described in order.
[0185] <Polymer A (resin)>
[0186] When the photosensitive layer is a negative photosensitive layer, the resin contained in the photosensitive layer is also referred to as polymer A in particular.
[0187] Examples of the polymer A include, but are not limited to, (meth)acrylic resins, styrene resins, epoxy resins, amide resins, amide epoxy resins, alkyd resins, phenolic resins, ester resins, urethane resins, and acid-modified epoxy acrylate resins obtained by reacting epoxy acrylate resins with acid anhydrides.
[0188] As the polymer A, a (meth)acrylic resin is preferred.
[0189] In the present invention, the (meth)acrylic resin refers to a resin having a constituent unit derived from a (meth)acrylic compound. In the (meth)acrylic resin, the content of the constituent unit derived from the (meth)acrylic compound is preferably 30% by mass or more, more preferably 50% by mass or more, and further preferably 60% by mass or more relative to the total mass of the (meth)acrylic resin.
[0190] As the polymer A, a polymer having a structural unit derived from a (meth)acrylic compound and a structural unit derived from a styrene compound is also preferred.
[0191] The polymer A is preferably an alkali-soluble resin.
[0192] From the viewpoint of achieving better resolution by suppressing swelling of the photosensitive layer by the developer, the acid value of the polymer A is preferably 250 mgKOH / g or less, more preferably less than 200 mgKOH / g, and even more preferably less than 190 mgKOH / g.
[0193] There is no particular restriction on the lower limit of the acid value of the polymer A. From the viewpoint of more excellent developability, the acid value of the polymer A is preferably 60 mgKOH / g or more, more preferably 80 mgKOH / g or more, and further preferably 120 mgKOH / g or more.
[0194] The acid value (mgKOH / g) is the mass [mg] of potassium hydroxide required to neutralize 1 g of a sample. The acid value can be calculated from the average content of the acid group in the compound, for example.
[0195] The acid value of the polymer A may be adjusted by the type of the structural unit constituting the polymer A and the content of the structural unit containing an acid group.
[0196] The weight average molecular weight of polymer A is preferably 5,000 to 500,000. A weight average molecular weight of 500,000 or less is preferred from the viewpoint of improving resolution and developability. The weight average molecular weight is more preferably 100,000 or less, and even more preferably 60,000 or less.
[0197] On the other hand, when the weight average molecular weight is 5,000 or more, it is preferred from the viewpoint of controlling the properties of the developed agglomerate and the properties of the unexposed film such as the edge fusibility and chipping when the photosensitive resin laminate is formed. The weight average molecular weight is more preferably 10,000 or more, further preferably 20,000 or more, and particularly preferably 30,000 or more. Edge fusibility refers to the degree to which the photosensitive layer easily overflows from the end face of the roll when the photosensitive resin laminate is wound into a roll. Chipping refers to the ease with which chips fly when the unexposed film is cut with a cutter. If the chips adhere to the upper surface of the photosensitive resin laminate, etc., they are transferred to the mask in the subsequent exposure process, etc., causing defective products.
[0198] In addition, the photosensitive resin laminate refers to a laminate obtained by laminating a transfer film and a substrate.
[0199] The dispersity of polymer A is preferably 1.0 to 6.0, more preferably 1.0 to 5.0, further preferably 1.0 to 4.0, and particularly preferably 1.0 to 3.0. In the present invention, the dispersity is the ratio of the weight average molecular weight to the number average molecular weight (weight average molecular weight / number average molecular weight). In the present invention, the weight average molecular weight and the number average molecular weight are values measured using gel permeation chromatography.
[0200] From the viewpoint of suppressing the deterioration of line width or resolution when the focus position is offset during exposure, the photosensitive layer preferably has polymer A containing constituent units based on monomers having aromatic hydrocarbon groups. In addition, as such aromatic hydrocarbon groups, for example, substituted or unsubstituted phenyl groups and substituted or unsubstituted aralkyl groups can be cited. The content of constituent units based on monomers having aromatic hydrocarbon groups in polymer A is preferably 20% by mass or more, more preferably 30% by mass or more relative to the total mass of polymer A. As an upper limit, it is not particularly limited, but is preferably 95% by mass or less, more preferably 85% by mass or less. In addition, when multiple polymers A are included, it is preferred that the average value of the content of constituent units based on monomers having aromatic hydrocarbon groups is within the above range.
[0201] As monomers having aromatic hydrocarbon groups, for example, monomers having aralkyl groups, styrene and polymerizable styrene derivatives (for example, methyl styrene, vinyl toluene, tert-butoxy styrene, acetoxy styrene, 4-vinyl benzoic acid, styrene dimer and styrene trimer, etc.) can be cited. Among them, monomers or styrene having aralkyl groups are preferred. In one embodiment, when the monomer component having an aromatic hydrocarbon group in polymer A is styrene, the content of the constituent unit based on styrene is preferably 20% to 70% by mass relative to the total mass of polymer A, more preferably 25% to 65% by mass, further preferably 30% to 60% by mass, and particularly preferably 30% to 55% by mass. In addition, when the photosensitive layer contains a plurality of polymers A, the content of the constituent unit having an aromatic hydrocarbon group is obtained as a weight average.
[0202] Examples of the aralkyl group include a substituted or unsubstituted phenylalkyl group (excluding benzyl) and a substituted or unsubstituted benzyl group, and a substituted or unsubstituted benzyl group is preferred.
[0203] Examples of the monomer having a phenylalkyl group include phenylethyl (meth)acrylate and the like.
[0204] As the monomer having a benzyl group, there can be mentioned a (meth) acrylate having a benzyl group, such as benzyl (meth) acrylate and benzyl (meth) acrylate chloride, etc.; a vinyl monomer having a benzyl group, such as vinyl benzyl chloride and vinyl benzyl alcohol, etc. Among them, benzyl (meth) acrylate is preferred. In one embodiment, when the monomer component having an aromatic hydrocarbon group in polymer A is benzyl (meth) acrylate, the content of the constituent unit based on benzyl (meth) acrylate is preferably 50% to 95% by mass relative to the total mass of polymer A, more preferably 60% to 90% by mass, further preferably 70% to 90% by mass, and particularly preferably 75% to 90% by mass.
[0205] The polymer A including a structural unit based on a monomer having an aromatic hydrocarbon group is preferably obtained by polymerizing a monomer having an aromatic hydrocarbon group and at least one first monomer described below and / or at least one second monomer described below.
[0206] The polymer A not including a structural unit based on a monomer having an aromatic hydrocarbon group is preferably obtained by polymerizing at least one first monomer described below, and more preferably by copolymerizing at least one first monomer and at least one second monomer described below.
[0207] The first monomer is a monomer having a carboxyl group in the molecule. Examples of the first monomer include (meth)acrylic acid, fumaric acid, cinnamic acid, crotonic acid, itaconic acid, 4-vinylbenzoic acid, maleic anhydride, and maleic acid half ester. Among these, (meth)acrylic acid is preferred.
[0208] The content of the structural unit based on the first monomer in the polymer A is preferably 5 to 50% by mass, more preferably 10 to 40% by mass, and further preferably 15 to 30% by mass, based on the total mass of the polymer A.
[0209] From the viewpoint of showing good developability, controlling edge melting properties, etc., the above content is preferably 5% by mass or more. From the viewpoint of high resolution and curling shape of the photoresist pattern, and further from the viewpoint of chemical resistance of the photoresist pattern, the above content is preferably 50% by mass or less.
[0210] The second monomer is a non-acidic monomer having at least one polymerizable unsaturated group in the molecule. Examples of the second monomer include (meth)acrylate methyl, (meth)acrylate ethyl, (meth)acrylate n-propyl, (meth)acrylate isopropyl, (meth)acrylate n-butyl, (meth)acrylate isobutyl, (meth)acrylate tert-butyl, (meth)acrylate 2-hydroxyethyl, (meth)acrylate 2-hydroxypropyl, (meth)acrylate cyclohexyl, and (meth)acrylate 2-ethylhexyl (meth)acrylate ...
[0211] The content of the structural unit based on the second monomer in the polymer A is preferably 5 to 60% by mass, more preferably 15 to 50% by mass, and further preferably 17 to 45% by mass, based on the total mass of the polymer A.
[0212] When the polymer A contains a structural unit based on a monomer having an aralkyl group and / or a structural unit based on a styrene monomer, it is preferred from the viewpoint of suppressing the deterioration of line width or resolution when the focus position is shifted during exposure. For example, a copolymer containing a structural unit based on methacrylic acid, a structural unit based on benzyl methacrylate, and a structural unit based on styrene, a copolymer containing a structural unit based on methacrylic acid, a structural unit based on methyl methacrylate, a structural unit based on benzyl methacrylate, and a structural unit based on styrene, etc. are preferred.
[0213] In one embodiment, the polymer A preferably comprises 25% to 55% by mass of constituent units based on a monomer having an aromatic hydrocarbon group, 20% to 35% by mass of constituent units based on the first monomer, and 15% to 45% by mass of constituent units based on the second monomer. In another embodiment, the polymer preferably comprises 70% to 90% by mass of constituent units based on a monomer having an aromatic hydrocarbon group, and 10% to 25% by mass of constituent units based on the first monomer.
[0214] The polymer A may have any of a linear structure, a branched structure, and an alicyclic structure in the side chain. By using a monomer containing a group having a branched structure in the side chain or a monomer containing a group having an alicyclic structure in the side chain, the branched structure or the alicyclic structure can be introduced into the side chain of the polymer A. The group having an alicyclic structure may be monocyclic or polycyclic.
[0215] Specific examples of the monomer containing a group having a branched structure in the side chain include, for example, isopropyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, isoamyl (meth)acrylate, tert-amyl (meth)acrylate, sec-amyl (meth)acrylate, 2-octyl (meth)acrylate, 3-octyl (meth)acrylate, and tert-octyl (meth)acrylate. Among these, isopropyl (meth)acrylate, isobutyl (meth)acrylate, and tert-butyl methacrylate are preferred, and isopropyl methacrylate or tert-butyl methacrylate is more preferred.
[0216] Specific examples of the monomer containing a group having an alicyclic structure in the side chain include monomers having a monocyclic aliphatic hydrocarbon group and monomers having a polycyclic aliphatic hydrocarbon group. In addition, as a monomer containing a group having an alicyclic structure in the side chain, (meth)acrylates having an alicyclic hydrocarbon group having 5 to 20 carbon atoms can be mentioned. More specific examples include (bicyclo[2.2.1]heptyl-2-(meth)acrylate, 1-adamantyl (meth)acrylate, 2-adamantyl (meth)acrylate, 3-methyl-1-adamantyl (meth)acrylate, 3,5-dimethyl-1-adamantyl (meth)acrylate, 3-ethyladamantyl (meth)acrylate, 3-methyl-5-ethyl-1-adamantyl (meth)acrylate, 3,5,8-triethyl-1-adamantyl (meth)acrylate, 3,5-dimethyl-8-ethyl-1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, 2-ethyl-2-adamantyl (meth)acrylate, methyl (meth)acrylate, 1-mentholyl (meth)acrylate, tricyclodecane (meth)acrylate, 3-hydroxy-2,6,6-trimethyl-bicyclo〔3.1.1〕heptyl (meth)acrylate, 3,7,7-trimethyl-4-hydroxy-bicyclo〔4.1.0〕heptyl (meth)acrylate, (nor)bornyl (meth)acrylate, isobornyl (meth)acrylate, fenchyl (meth)acrylate, 2,2,5-trimethylcyclohexyl (meth)acrylate and cyclohexyl (meth)acrylate.
[0217] Among them, the monomer containing a group having an alicyclic structure in the side chain is preferably cyclohexyl (meth)acrylate, (nor)bornyl (meth)acrylate, isobornyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-adamantyl (meth)acrylate, fenchyl (meth)acrylate, 1-mentholyl (meth)acrylate or tricyclodecane (meth)acrylate, and more preferably cyclohexyl (meth)acrylate, (nor)bornyl (meth)acrylate, isobornyl (meth)acrylate, 2-adamantyl (meth)acrylate or tricyclodecane (meth)acrylate.
[0218] The polymer A contained in the photosensitive layer may be one kind or two or more kinds.
[0219] When two or more polymers A are included, it is preferred that two polymers A including structural units based on a monomer having an aromatic hydrocarbon group are included, or that a polymer A including structural units based on a monomer having an aromatic hydrocarbon group and a polymer A not including structural units based on a monomer having an aromatic hydrocarbon group are included. In the latter case, the proportion of the polymer A including structural units based on a monomer having an aromatic hydrocarbon group is preferably 50% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, and particularly preferably 90% by mass or more, relative to the total mass of the polymer A.
[0220] Furthermore, from the viewpoint of sensitivity and resolution, the photosensitive layer preferably contains an alkali-soluble resin having a crosslinkable group.
[0221] From the viewpoint of developability, sensitivity, and resolution, the crosslinkable group is preferably a polymerizable group.
[0222] The polymerizable group is not particularly limited as long as it is a group that participates in the polymerization reaction, and examples thereof include groups having ethylenically unsaturated groups such as vinyl, (meth)acryloyl, styryl and maleimide groups; and groups having cationic polymerizable groups such as epoxy and oxetane groups.
[0223] As the polymerizable group, a group having an ethylenically unsaturated group is preferred, and an acryloyl group or a methacryloyl group is more preferred.
[0224] The alkali-soluble resin having a crosslinkable group is preferably an acrylic resin having an ethylenically unsaturated group, and more preferably an acrylic resin containing a structural unit having an ethylenically unsaturated group.
[0225] The synthesis of polymer A is preferably carried out by adding an appropriate amount of free radical polymerization initiators such as benzoyl peroxide and azoisobutyronitrile to a solution prepared by diluting the above-mentioned one or more monomers with solvents such as acetone, methyl ethyl ketone and isopropanol, and heating and stirring. Sometimes, a part of the mixture is added dropwise to the reaction solution while the synthesis is carried out. After the reaction is completed, a solvent is sometimes further added to adjust the desired concentration. As a synthesis method, in addition to solution polymerization, block polymerization, suspension polymerization or emulsion polymerization can be used.
[0226] The glass transition temperature Tg of polymer A is preferably 30°C to 135°C. By using polymer A having a Tg of 135°C or less, it is possible to suppress the deterioration of line width or resolution when the focus position is shifted during exposure. From this viewpoint, the Tg of polymer A is more preferably 130°C or less, further preferably 120°C or less, and particularly preferably 110°C or less. Furthermore, from the viewpoint of improving edge melting resistance, it is preferred to use polymer A having a Tg of 30°C or more. From this viewpoint, the Tg of polymer A is more preferably 40°C or more, further preferably 50°C or more, particularly preferably 60°C or more, and most preferably 70°C or more.
[0227] The photosensitive layer may contain, as the polymer A, other resins than those described above.
[0228] Examples of other resins include acrylic resins, styrene-acrylic copolymers, polyurethane resins, polyvinyl alcohol, polyvinyl formaldehyde, polyamide resins, polyester resins, polyamide resins, epoxy resins, polyacetal resins, polyhydroxystyrene resins, polyimide resins, polybenzoxazole resins, polysiloxane resins, polyethyleneimine, polyallylamine, and polyalkylene glycol.
[0229] As the polymer A, an alkali-soluble resin described in the section of the thermoplastic resin layer to be described later may be used.
[0230] The content of polymer A is preferably 10% to 90% by mass, more preferably 30% to 70% by mass, and further preferably 40% to 60% by mass relative to the total mass of the photosensitive layer. If the content of polymer A relative to the total mass of the photosensitive layer is 90% by mass or less, the development time can be controlled, so it is preferred. On the other hand, if the content of polymer A relative to the total mass of the photosensitive layer is 10% by mass or more, the edge melting resistance is improved, so it is preferred.
[0231] <Polymerizable Compound>
[0232] When the photosensitive layer is a negative photosensitive layer, the photosensitive layer preferably contains a polymerizable compound having a polymerizable group. In the present invention, the "polymerizable compound" refers to a compound different from the above-mentioned polymer A that is polymerized by the action of a polymerization initiator described below.
[0233] The polymerizable group possessed by the polymerizable compound is not particularly limited as long as it is a group that participates in the polymerization reaction. Examples thereof include groups having ethylenically unsaturated groups such as vinyl, (meth)acryloyl, styryl and maleimide groups; and groups having cationic polymerizable groups such as epoxy and oxetane groups.
[0234] As the polymerizable group, a group having an ethylenically unsaturated group is preferred, and a (meth)acryloyl group is more preferred.
[0235] As the polymerizable compound, a compound having one or more ethylenically unsaturated groups (ethylenically unsaturated compounds) is preferred, and a compound having two or more ethylenically unsaturated groups in one molecule (polyfunctional ethylenically unsaturated compounds) is more preferred, from the viewpoint of providing a better photosensitivity to the photosensitive layer.
[0236] Furthermore, from the viewpoint of achieving better resolution and releasability, the number of ethylenically unsaturated groups contained in one molecule of the ethylenically unsaturated compound is preferably 6 or less, more preferably 3 or less, and even more preferably 2 or less.
[0237] From the viewpoint of achieving a better balance between the photosensitivity, resolution and peeling properties of the photosensitive layer, the photosensitive layer preferably contains a bifunctional or trifunctional ethylenically unsaturated compound having two or three ethylenically unsaturated groups in one molecule, and more preferably contains a bifunctional ethylenically unsaturated compound having two ethylenically unsaturated groups in one molecule.
[0238] From the viewpoint of excellent stripping property, the content of the bifunctional ethylenically unsaturated compound is preferably 20% by mass or more relative to the total mass of the polymerizable compound, more preferably more than 40% by mass, and further preferably more than 55% by mass. The upper limit of the content of the bifunctional ethylenically unsaturated compound is not particularly limited and can be 100% by mass. That is, the polymerizable compound can be all bifunctional ethylenically unsaturated compounds.
[0239] Furthermore, as the ethylenically unsaturated compound, a (meth)acrylate compound having a (meth)acryloyl group as a polymerizable group is preferred.
[0240] (Polymerizable compound B1)
[0241] The photosensitive layer also preferably contains a polymerizable compound B1 having an aromatic ring and two ethylenically unsaturated groups. The polymerizable compound B1 is a bifunctional ethylenically unsaturated compound having one or more aromatic rings in one molecule among the above-mentioned polymerizable compounds.
[0242] In the photosensitive layer, from the viewpoint of better resolution, the mass ratio of the content of the polymerizable compound B1 relative to the total mass of the polymerizable compound is preferably 40% or more, more preferably 50% or more, further preferably 55% or more, and particularly preferably 60% or more. The upper limit is not particularly limited, but from the viewpoint of peelability, it is, for example, 100% or less, preferably 99% or less, more preferably 95% or less, further preferably 90% or less, and particularly preferably 85% or less.
[0243] Examples of the aromatic ring possessed by the polymerizable compound B1 include aromatic hydrocarbon rings such as a benzene ring, a naphthalene ring, and an anthracene ring, aromatic heterocyclic rings such as a thiophene ring, a furan ring, a pyrrole ring, an imidazole ring, a triazole ring, and a pyridine ring, and condensed rings thereof, preferably an aromatic hydrocarbon ring, more preferably a benzene ring. The aromatic ring may have a substituent.
[0244] The polymerizable compound B1 may have only one aromatic ring, or may have two or more aromatic rings.
[0245] From the viewpoint of improving the resolution by suppressing the swelling of the photosensitive layer due to the developer, the polymerizable compound B1 preferably has a bisphenol structure.
[0246] Examples of the bisphenol structure include a bisphenol A structure derived from bisphenol A (2,2-bis(4-hydroxyphenyl)propane), a bisphenol F structure derived from bisphenol F (2,2-bis(4-hydroxyphenyl)methane), and a bisphenol B structure derived from bisphenol B (2,2-bis(4-hydroxyphenyl)butane), and a bisphenol A structure is preferred.
[0247] Examples of the polymerizable compound B1 having a bisphenol structure include a compound having a bisphenol structure and two polymerizable groups (preferably (meth)acryloyl groups) bonded to both ends of the bisphenol structure.
[0248] The two ends of the bisphenol structure may be directly bonded to the two polymerizable groups, or may be bonded via one or more alkyleneoxy groups. As the alkyleneoxy groups added to the two ends of the bisphenol structure, ethyleneoxy groups or propyleneoxy groups are preferred, and ethyleneoxy groups are more preferred. The number of alkyleneoxy groups added to the bisphenol structure is not particularly limited, but is preferably 4 to 16 per molecule, and more preferably 6 to 14.
[0249] The polymerizable compound B1 having a bisphenol structure is described in paragraphs
[0072] to
[0080] of JP-A-2016-224162, and the contents described in the publication are incorporated into the present specification.
[0250] As the polymerizable compound B1, a bifunctional ethylenically unsaturated compound having a bisphenol A structure is preferred, and 2,2-bis(4-((meth)acryloyloxypolyalkoxy)phenyl)propane is more preferred.
[0251] Examples of 2,2-bis(4-((meth)acryloxypolyalkoxy)phenyl)propane include 2,2-bis(4-(methacryloxydiethoxy)phenyl)propane (FA-324M, manufactured by Hitachi Chemical Co., Ltd.), 2,2-bis(4-(methacryloxyethoxypropoxy)phenyl)propane, ethoxylated bisphenol A dimethacrylate (NK Ester BPE-500, average number of ethylene oxide chain repetitions: 10, manufactured by Shin-Nakamura Chemical Co., Ltd.), 2,2-bis(4-(methacryloxydodecylethoxytetrapropoxy)phenyl)propane (FA-3200MY, manufactured by Hitachi Chemical Co., Ltd.), ethoxylated bisphenol A dimethacrylate (NK Ester BPE-1300N, average number of ethylene oxide chain repetitions: 30, manufactured by Shin-Nakamura Chemical Co., Ltd.), and 2,2-bis(4-(methacryloxydodecylethoxytetrapropoxy)phenyl)propane (FA-3200MY, manufactured by Hitachi Chemical Co., Ltd.). Co., Ltd.), ethoxylated bisphenol A dimethacrylate (NK Ester BPE-200, average repeating number of ethylene oxide chain 4, manufactured by Shin-Nakamura Chemical Co., Ltd.), ethoxylated bisphenol A dimethacrylate (NK Ester BPE-100, average repeating number of ethylene oxide chain 2.6, manufactured by Shin-Nakamura Chemical Co., Ltd.) and ethoxylated bisphenol A diacrylate (NK Ester A-BPE-10, average repeating number of ethylene oxide chain 10, manufactured by Shin-Nakamura Chemical Co., Ltd.).
[0252] As the polymerizable compound B1, a compound represented by the following general formula (B1) is also preferred.
[0253] [Chemical formula 1]
[0254]
[0255] In the general formula (B1), R1 and R2 each independently represent a hydrogen atom or a methyl group. A represents C2H4. B represents C3H6. n1 and n3 each independently represent an integer of 1 to 39, and n1+n3 represents an integer of 2 to 40. n2 and n4 each independently represent an integer of 0 to 29, and n2+n4 represents an integer of 0 to 30. The arrangement of the structural units of -(AO)- and -(BO)- may be random or blocky. Moreover, in the case of a block, either of -(AO)- and -(BO)- may be on the biphenyl side.
[0256] In one embodiment, n1+n2+n3+n4 is preferably 2 to 20, more preferably 2 to 16, and even more preferably 4 to 12. Furthermore, n2+n4 is preferably 0 to 10, more preferably 0 to 4, even more preferably 0 to 2, and particularly preferably 0.
[0257] The polymerizable compound B1 contained in the photosensitive layer may be one kind or two or more kinds.
[0258] From the viewpoint of better resolution, the content of the polymerizable compound B1 is preferably 10% by mass or more, more preferably 20% by mass or more, relative to the total mass of the photosensitive layer. The upper limit is not particularly limited, but from the viewpoint of transferability and edge melting (phenomenon in which the photosensitive resin seeps out from the end of the transfer member), it is preferably 70% by mass or less, more preferably 60% by mass or less.
[0259] The photosensitive layer may contain a polymerizable compound other than the above-mentioned polymerizable compound B1.
[0260] The polymerizable compounds other than the polymerizable compound B1 are not particularly limited and can be appropriately selected from known compounds, for example, compounds having one ethylenically unsaturated group in one molecule (monofunctional ethylenically unsaturated compounds), bifunctional ethylenically unsaturated compounds without an aromatic ring, and trifunctional or higher ethylenically unsaturated compounds.
[0261] Examples of the monofunctional ethylenically unsaturated compound include ethyl (meth)acrylate, ethylhexyl (meth)acrylate, 2-(meth)acryloyloxyethyl succinate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, and phenoxyethyl (meth)acrylate.
[0262] Examples of the bifunctional ethylenically unsaturated compound having no aromatic ring include alkylene glycol di(meth)acrylate, polyalkylene glycol di(meth)acrylate, urethane di(meth)acrylate, and trimethylolpropane diacrylate.
[0263] Examples of the alkylene glycol di(meth)acrylate include tricyclodecane dimethanol diacrylate (A-DCP, manufactured by Shin-Nakamura Chemical Co., Ltd.), tricyclodecane dimethanol dimethacrylate (DCP, manufactured by Shin-Nakamura Chemical Co., Ltd.), 1,9-nonanediol diacrylate (A-NOD-N, manufactured by Shin-Nakamura Chemical Co., Ltd.), 1,6-hexanediol diacrylate (A-HD-N, manufactured by Shin-Nakamura Chemical Co., Ltd.), ethylene glycol dimethacrylate, 1,10-decanediol diacrylate and neopentyl glycol di(meth)acrylate.
[0264] As a polyalkylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, and polypropylene glycol di(meth)acrylate are mentioned, for example.
[0265] Examples of urethane di(meth)acrylates include propylene oxide-modified urethane di(meth)acrylates and ethylene oxide- and propylene oxide-modified urethane di(meth)acrylates. Examples of commercially available products include 8UX-015A (manufactured by Taisei Fine Chemical Co., Ltd.), UA-32P (manufactured by Shin-Nakamura Chemical Co., Ltd.), and UA-1100H (manufactured by Shin-Nakamura Chemical Co., Ltd.).
[0266] From the viewpoint of better resolution and photoresist stripping properties, the content of the bifunctional ethylenically unsaturated compound is preferably 20% by mass or more, more preferably 30% by mass or more, and further preferably 40% by mass or more relative to the total mass of the negative photosensitive layer. From the viewpoint of transferability and edge melting (phenomenon of photosensitive composition oozing out from the end of the transfer member), the upper limit is preferably 70% by mass or less, and more preferably 60% by mass or less.
[0267] From the viewpoint of better resolution and photoresist stripping properties, the content of the bifunctional ethylenically unsaturated compound is preferably 40% by mass or more, more preferably 60% by mass or more, and further preferably 80% by mass or more relative to the total mass of the polymerizable compound having an ethylenically unsaturated group. From the viewpoint of transferability and edge melting (phenomenon in which the photosensitive composition oozes out from the end of the transfer film), the upper limit is preferably 100% by mass or less, and more preferably 90% by mass or less.
[0268] Examples of trifunctional or higher ethylenically unsaturated compounds include dipentaerythritol (tri / tetra / penta / hexa) (meth)acrylate, pentaerythritol (tri / tetra) (meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, trimethylolethane tri(meth)acrylate, isocyanuric acid tri(meth)acrylate, glycerol tri(meth)acrylate, and alkylene oxide-modified products thereof.
[0269] Here, “(tri / tetra / penta / hexa) (meth)acrylate” is a concept including tri(meth)acrylate, tetra(meth)acrylate, penta(meth)acrylate and hexa(meth)acrylate, and “(tri / tetra) (meth)acrylate” is a concept including tri(meth)acrylate and tetra(meth)acrylate.
[0270] In one embodiment, the photosensitive layer also preferably contains the above-mentioned polymerizable compound B1 and a trifunctional or higher ethylenically unsaturated compound, and more preferably contains the above-mentioned polymerizable compound B1 and two or more trifunctional or higher ethylenically unsaturated compounds. In this case, the mass ratio of the polymerizable compound B1 to the trifunctional or higher ethylenically unsaturated compound is preferably (total mass of the polymerizable compound B1): (total mass of the trifunctional or higher ethylenically unsaturated compounds) = 1:1 to 5:1, more preferably 1.2:1 to 4:1, and further preferably 1.5:1 to 3:1.
[0271] Furthermore, in one aspect, the photosensitive layer preferably contains the above-mentioned polymerizable compound B1 and two or more trifunctional ethylenically unsaturated compounds.
[0272] Examples of the alkylene oxide-modified products of trifunctional or higher ethylenic unsaturated compounds include caprolactone-modified (meth)acrylate compounds (KAYARAD (registered trademark) DPCA-20 manufactured by Nippon Kayaku Co., Ltd., A-9300-1CL manufactured by Shin-Nakamura Chemical Co., Ltd., etc.), alkylene oxide-modified (meth)acrylate compounds (KAYARAD RP-1040 manufactured by Nippon Kayaku Co., Ltd., ATM-35E and A-9300 manufactured by Shin-Nakamura Chemical Co., Ltd., EBECRYL (registered trademark) 135 manufactured by DAICEL-ALLNEX LTD., etc.), ethoxylated glyceryl trimethacrylate (Shin-Nakamura Chemical Co., Ltd. A-GLY-9E, etc.), ARONIX (registered trademark) TO-2349 (manufactured by TOAGOSEI CO., LTD.), ARONIX M-520 (manufactured by TOAGOSEI CO., LTD.) and ARONIX M-510 (manufactured by TOAGOSEI CO., LTD.).
[0273] Furthermore, as the polymerizable compound, a polymerizable compound having an acid group (carboxyl group, etc.) can be used. The above acid group can form an acid anhydride group. As the polymerizable compound having an acid group, ARONIX (registered trademark) TO-2349 (manufactured by TOAGOSEI CO., LTD.), ARONIX (registered trademark) M-520 (manufactured by TOAGOSEI CO., LTD.) and ARONIX (registered trademark) M-510 (manufactured by TOA GOSEI CO., LTD.) can be cited.
[0274] As the polymerizable compound having an acid group, for example, the polymerizable compounds having an acid group described in paragraphs
[0025] to
[0030] of JP-A-2004-239942 can be used.
[0275] The polymerizable compound contained in the photosensitive layer may be one kind or two or more kinds.
[0276] The content of the polymerizable compound is preferably 10% by mass to 70% by mass, more preferably 15% by mass to 70% by mass, and further preferably 20% by mass to 70% by mass, based on the total mass of the photosensitive layer.
[0277] The molecular weight (weight average molecular weight when having a molecular weight distribution) of the polymerizable compound (including polymerizable compound B1) is preferably 200 to 3,000, more preferably 280 to 2,200, and even more preferably 300 to 2,200.
[0278] <Polymerization Initiator>
[0279] When the photosensitive layer is a negative photosensitive layer, the photosensitive layer also preferably contains a polymerization initiator.
[0280] The polymerization initiator can be selected according to the form of the polymerization reaction, and examples thereof include a thermal polymerization initiator and a photopolymerization initiator.
[0281] The polymerization initiator may be a radical polymerization initiator or a cationic polymerization initiator.
[0282] The photosensitive layer preferably contains a photopolymerization initiator.
[0283] The photopolymerization initiator is a compound that initiates polymerization of a polymerizable compound upon receiving active light such as ultraviolet rays, visible rays, and X-rays. The photopolymerization initiator is not particularly limited, and a known photopolymerization initiator can be used.
[0284] Examples of the photopolymerization initiator include a photoradical polymerization initiator and a photocationic polymerization initiator, and a photoradical polymerization initiator is preferred.
[0285] Examples of the photoradical polymerization initiator include a photopolymerization initiator having an oxime ester structure, a photopolymerization initiator having an α-aminoalkylphenone structure, a photopolymerization initiator having an α-hydroxyalkylphenone structure, a photopolymerization initiator having an acylphosphine oxide structure, and a photopolymerization initiator having an N-phenylglycine structure.
[0286] Furthermore, from the viewpoints of photosensitivity, visibility of the exposed and non-exposed parts, and resolution, the photosensitive layer preferably contains at least one selected from 2,4,5-triarylimidazole dimers and derivatives thereof as a photoradical polymerization initiator. In addition, the two 2,4,5-triarylimidazole structures in the 2,4,5-triarylimidazole dimer and derivatives thereof may be the same or different.
[0287] Examples of the derivatives of 2,4,5-triarylimidazole dimers include 2-(o-chlorophenyl)-4,5-diphenylimidazole dimer, 2-(o-chlorophenyl)-4,5-di(methoxyphenyl)imidazole dimer, 2-(o-fluorophenyl)-4,5-diphenylimidazole dimer, 2-(o-methoxyphenyl)-4,5-diphenylimidazole dimer and 2-(p-methoxyphenyl)-4,5-diphenylimidazole dimer.
[0288] As the photoradical polymerization initiator, for example, polymerization initiators described in paragraphs
[0031] to
[0042] of JP-A-2011-95716 and paragraphs
[0064] to
[0081] of JP-A-2015-14783 can be used.
[0289] Examples of the photoradical polymerization initiator include ethyl dimethylaminobenzoate (DBE, CAS No. 10287-53-3), benzoin methyl ether, (p,p'-dimethoxybenzyl) anisate, TAZ-110 (trade name: manufactured by Midori Kagaku Co., Ltd.), benzophenone, 4,4'-bis(diethylamino)benzophenone, TAZ-111 (trade name: manufactured by Midori Kagaku Co., Ltd.), Irgacure OXE01, OXE02, OXE03, OXE04 (manufactured by BASF), Omnirad 651 and 369 (trade names: manufactured by IGM Resins BV), and 2,2'-bis(2-chlorophenyl)-4,4',5,5'-tetraphenyl-1,2'-biimidazole (manufactured by Tokyo Chemical Industry Co., Ltd.).
[0290] Examples of commercially available photoradical polymerization initiators include 1-[4-(phenylthio)phenyl]-1,2-octanedione-2-(0-benzoyloxime) (trade name: IRGACURE (registered trademark) OXE-01, manufactured by BASF), 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone-1-(0-acetyloxime) (trade name: IRGACURE OXE-02, manufactured by BASF), IRGACURE OXE-03 (manufactured by BASF), IRGACURE OXE-04 (manufactured by BASF), 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone (trade name: 0mnirad379EG, manufactured by IGM Resins BV), 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one (trade name: Omnirad907, manufactured by IGM Resins BV), 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)benzyl]phenyl)-2-methylpropan-1-one (trade name: Omnirad127, manufactured by IGM Resins BV), 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone-1 (trade name: Omnirad369, manufactured by IGM Resins BV), 2-hydroxy-2-methyl-1-phenylpropan-1-one (trade name: Omnirad1173, manufactured by IGM Resins BV), 1-hydroxycyclohexyl phenyl ketone (trade name: Omnirad184, manufactured by IGM Resins BV), BV), 2,2-dimethoxy-1,2-diphenylethane-1-one (trade name: Omnirad 651, manufactured by IGM Resins BV), 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (trade name: Omnirad TPO H, manufactured by IGM Resins BV), bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (trade name: Omnirad 819, manufactured by IGM Resins BV), oxime ester-based photopolymerization initiator (trade name: Lunar 6, manufactured by DKSH Japan K.K.), 2,2'-bis(2-chlorophenyl)-4,4',5,5'-tetraphenylbiimidazole (2-(2-chlorophenyl)-4,5-diphenylimidazole dimer) (trade name: B-CIM, manufactured by Hampford) and 2-(o-chlorophenyl)-4,5-diphenylimidazole dimer (trade name: BCTB, manufactured by Tokyo Chemical Industry Co., Ltd.Company), 1-[4-(phenylthio)phenyl]-3-cyclopentylpropane-1,2-dione-2-(O-benzoyl oxime) (trade name: TR-PBG-305, manufactured by Changzhou Tronly NewFlectronic Materials CO., LTD.), 1,2-propanedione, 3-cyclohexyl-1-[9-ethyl-6-(2-furylcarbonyl)-9H-carbazole-3-yl]-, 2-(O-acetyl oxime) (trade name: TR-PBG-326, manufactured by Changzhou TronlyNew Electronic Materials CO., LTD.) and 3-cyclohexyl-1-(6-(2-(benzoyloxyimino)octanoyl)-9-ethyl-9H-carbazole-3-yl)-propane-1,2-dione-2-(O-benzoyl oxime) (trade name: TR-PBG-391, manufactured by Changzhou Tronly New Electronic Materials CO., LTD.).
[0291] A photocationic polymerization initiator (photoacid generator) is a compound that generates an acid upon receiving active light. As a photocationic polymerization initiator, a compound that generates an acid upon sensing active light with a wavelength of 300 nm or more, preferably 300 to 450 nm, is preferred, but its chemical structure is not limited. In addition, as for a photocationic polymerization initiator that is not directly responsive to active light with a wavelength of 300 nm or more, as long as it is a compound that generates an acid upon sensing active light with a wavelength of 300 nm or more by using it in combination with a sensitizer, it can also be preferably used in combination with a sensitizer.
[0292] As the photocationic polymerization initiator, a photocationic polymerization initiator that generates an acid with a pKa of 4 or less is preferred, a photocationic polymerization initiator that generates an acid with a pKa of 3 or less is more preferred, and a photocationic polymerization initiator that generates an acid with a pKa of 2 or less is particularly preferred. The lower limit of pKa is not particularly specified, but is preferably -10.0 or more, for example.
[0293] Examples of the photocationic polymerization initiator include ionic photocationic polymerization initiators and nonionic photocationic polymerization initiators.
[0294] Examples of the ionic photocationic polymerization initiator include onium salt compounds such as diaryliodonium salts and triarylsulfonium salts, and quaternary ammonium salts.
[0295] As the ionic photocationic polymerization initiator, the ionic photocationic polymerization initiators described in paragraphs
[0114] to
[0133] of JP-A-2014-085643 can be used.
[0296] As nonionic photocationic polymerization initiators, for example, trichloromethyl-s-triazines, diazomethane compounds, imide sulfonate compounds and oxime sulfonate compounds can be cited. As trichloromethyl-s-triazines, diazomethane compounds and imide sulfonate compounds, the compounds described in paragraphs
[0083] to
[0088] of Japanese Patent Publication No. 2011-221494 can be used. And, as oxime sulfonate compounds, the compounds described in paragraphs
[0084] to
[0088] of International Publication No. 2018 / 179640 can be used.
[0297] The photosensitive layer preferably contains a photoradical polymerization initiator, and more preferably contains at least one selected from 2,4,5-triarylimidazole dimers and derivatives thereof.
[0298] The polymerization initiator contained in the photosensitive layer may be one kind or two or more kinds.
[0299] The content of the polymerization initiator (preferably a photopolymerization initiator) is not particularly limited, but is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and further preferably 1.0% by mass or more relative to the total mass of the photosensitive layer. The upper limit is not particularly limited, but is preferably 20% by mass or less, further preferably 15% by mass or less, and further preferably 10% by mass or less relative to the total mass of the negative photosensitive layer.
[0300] <Pigment>
[0301] From the viewpoint of visibility of the exposed and non-exposed portions, pattern visibility after development, and resolution, the photosensitive layer also preferably includes a pigment (also referred to as "pigment N") whose maximum absorption wavelength is 450 nm or more in the wavelength range of 400 nm to 780 nm during color development and whose maximum absorption wavelength changes by acid, alkali, or free radicals. If pigment N is included, although the detailed mechanism is unclear, the adhesion with the adjacent layer (e.g., the intermediate layer) is improved, and the resolution is more excellent.
[0302] In the present invention, "the maximum absorption wavelength of a pigment changes by acid, alkali or free radicals" may refer to any of the following: a pigment in a coloring state is decolorized by acid, alkali or free radicals, a pigment in a decolorized state is colorized by acid, alkali or free radicals, and a pigment in a coloring state is changed into a coloring state of another hue.
[0303] Specifically, the pigment N can be a compound that changes from a bleached state to develop color by exposure, or a compound that changes from a bleached state to develop color by exposure. In this case, it can be a pigment that produces acid, alkali or free radicals in the photosensitive layer by exposure and these act, so that the color development or bleached state changes, or it can be a pigment that the state (such as pH) in the photosensitive layer changes by acid, alkali or free radicals, so that the color development or bleached state changes. In addition, it can also be a pigment that directly receives acid, alkali or free radicals as stimulation without exposure and the color development or bleached state changes.
[0304] Among them, from the viewpoint of visibility and resolution of the exposed and non-exposed areas, the dye N is preferably a dye whose maximum absorption wavelength changes by an acid or a radical, and more preferably a dye whose maximum absorption wavelength changes by a radical.
[0305] When the photosensitive layer is a negative photosensitive layer, the photosensitive layer preferably contains both a dye N whose maximum absorption wavelength changes due to radicals and a photoradical polymerization initiator from the viewpoint of visibility and resolution of exposed and non-exposed areas.
[0306] Furthermore, from the viewpoint of visibility of the exposed portion and the non-exposed portion, the dye N is preferably a dye that develops color by acid, base, or radical.
[0307] As an example of the color development mechanism of the pigment N, there can be cited a method in which a radical-reactive pigment, an acid-reactive pigment or an alkali-reactive pigment (for example, a colorless pigment) develops color by adding a photoradical polymerization initiator, a photocationic polymerization initiator (photoacid generator) or a photobase generator to a photosensitive layer and then exposing the layer to light, and then the radicals, acids or bases generated by the photoradical polymerization initiator, photocationic polymerization initiator or photobase generator are generated.
[0308] From the viewpoint of visibility of the exposed and non-exposed areas, the maximum absorption wavelength of the dye N in the wavelength range of 400 nm to 780 nm when developing color is preferably 550 nm or longer, more preferably 550 nm to 700 nm, and even more preferably 550 nm to 650 nm.
[0309] Furthermore, the pigment N may have only one maximum absorption wavelength in the wavelength range of 400 nm to 780 nm when developing color, or may have two or more. When the pigment N has two or more maximum absorption wavelengths in the wavelength range of 400 nm to 780 nm when developing color, the maximum absorption wavelength with the highest absorbance among the two or more maximum absorption wavelengths may be 450 nm or more.
[0310] The maximum absorption wavelength of the dye N is obtained by measuring the transmission spectrum of a solution containing the dye N (liquid temperature 25° C.) in the range of 400 to 780 nm using a spectrophotometer: UV3100 (manufactured by Shimadzu Corporation) in an atmospheric environment and detecting the wavelength (maximum absorption wavelength) at which the light intensity is minimal.
[0311] Examples of dyes that develop or fade color by exposure include colorless compounds.
[0312] Examples of the dye that is discolored by exposure include colorless compounds, diarylmethane dyes, oxazine dyes, xanthene dyes, iminonaphthoquinone dyes, azomethine dyes, and anthraquinone dyes.
[0313] As the dye N, a colorless compound is preferred from the viewpoint of visibility of the exposed portion and the non-exposed portion.
[0314] Examples of the colorless compound include colorless compounds having a triarylmethane skeleton (triarylmethane-based dyes), colorless compounds having a spiropyran skeleton (spiropyran-based dyes), colorless compounds having a fluorane skeleton (fluorane-based dyes), colorless compounds having a diarylmethane skeleton (diarylmethane-based dyes), colorless compounds having a rhodamine lactam skeleton (rhodamine lactam dyes), colorless compounds having an indolylphthalide skeleton (indolylphthalide dyes), and colorless compounds having a colorless chrysopramine skeleton (colorless chrysopramine-based dyes).
[0315] Among them, the dye N is preferably a triarylmethane dye or a fluoran dye, and more preferably a colorless compound having a triphenylmethane skeleton (triphenylmethane dye) or a fluoran dye.
[0316] As a colorless compound, from the viewpoint of visibility of the exposure part and the non-exposure part, it is preferred to have a lactone ring, a sultone ring or a sultone ring. Thus, the lactone ring, the sultone ring or the sultone ring of the colorless compound can be reacted with the free radicals generated by the photo-radical polymerization initiator or the acid generated by the photo-cationic polymerization initiator to make the colorless compound into a closed-loop state and decolorize it, or the colorless compound is changed to an open-loop state and colorizes it. As a colorless compound, it is preferred to have a lactone ring, a sultone ring or a sultone ring and the lactone ring, the sultone ring or the sultone ring is opened by a free radical or an acid to develop color, and more preferably a lactone ring and the lactone ring is opened by a free radical or an acid to develop color.
[0317] Examples of the coloring matter N include the following dyes and colorless compounds.
[0318] In the pigment N, specific examples of the dye include brilliant green, ethyl violet, methyl green, crystal violet, basic fuchsine, methyl violet 2B, quinaldine red, rose bengal, metanil yellow, thymolsulfonphthalein, xylenol blue, methyl orange, p-methyl red, Congo red, benzopurpurine 4B, α-naphthyl red, Nile blue 2B, Nile blue A, methyl violet, malachite green, parafuchsin, Victoria pure blue-naphthalenesulfonate, Victoria pure blue BOH (manufactured by Hodogaya Chemical Co., Ltd.), Oil Blue #603 (manufactured by Orient Chemical Industries Co., Ltd.), Oil Pink #312 (manufactured by Orient Chemical Industries Co., Ltd.), and more. Chemical Industries Co., Ltd.), Oil Red 5B (Orient Chemical Industries Co., Ltd.), Oil Scarlet #308 (Orient Chemical Industries Co., Ltd.), Oil Red OG (Orient Chemical Industries Co., Ltd.), Oil Red RR (Orient Chemical Industries Co., Ltd.), Oil Green #502 (Orient Chemical Industries Co., Ltd.), Spilon Red BEH Special (Hodogaya Chemical Co., Ltd.), m-cresol purple, cresol red, rhodamine B, rhodamine 6G, sulforhodamine B, golden amine, 4-p-diethylaminophenyliminonaphthoquinone, 2-carboxyanilino-4-p-diethylaminophenyliminonaphthoquinone, 2-carboxystearylamino-4-p-N,N-bis(hydroxyethyl)amino-phenyliminonaphthoquinone, 1-phenyl-3-methyl-4-p-diethylaminophenylimino-5-pyrazolone and 1-β-naphthyl-4-p-diethylaminophenylimino-5-pyrazolone.
[0319] In the pigment N, specific examples of colorless compounds include p,p',p"-hexamethyltriaminotriphenylmethane (colorless crystal violet), Pergascript Blue SRB (manufactured by Ciba-Geigy), crystal violet lactone, malachite green lactone, benzoyl leuco-methylene blue, 2-(N-phenyl-N-methylamino)-6-(N-p-tolyl-N-ethyl)aminofluoran, 2-phenylamino-3-methyl-6-(N-ethyl-p-tolylamino)fluoran, 3,6-dimethoxyfluoran, 3-(N,N-diethylamino)-5-methyl-7-(N,N-dibenzylamino)fluoran, 3-(N-cyclohexyl-N-methylamino)-6-methyl fluoran, 3-(N,N-diethylamino)-6-methyl-7-phenylaminofluoran, 3-(N,N-diethylamino)-6-methyl-7-sulphoaminofluoran, 3-(N,N-diethylamino)-6-methyl-7-chlorofluoran, 3-(N,N-diethylamino)-6-methoxy-7-aminofluoran, 3-(N,N-diethylamino)-7-(4-chlorophenylamino)fluoran, 3-(N,N-diethylamino)-7-chlorofluoran, 3-(N,N-diethylamino)-7-(4-chlorophenylamino)fluoran, 3-(N,N-diethylamino)-7,8-benzofluoran, 3-(N,N-dibutylamino)-6-methyl-7-phenylaminofluoran, 3-(N,N-dibutylamino)-6-methyl-7-phenylaminofluoran, 3-piperidinyl-6-methyl-7-phenylaminofluoran, 3-pyrrolidinyl-6-methyl-7-phenylaminofluoran, 3,3-bis(1-ethyl-2-methylindol-3-yl)phthalide, 3,3-bis(1-ethyl-2-methylindol-3-yl)phthalide, (1-n-butyl-2-methylindol-3-yl)phthalide, 3,3-bis(p-dimethylaminophenyl)-6-dimethylaminophthalide, 3-(4-diethylamino-2-ethoxyphenyl)-3-(1-ethyl-2-methylindol-3-yl)-4-phthalide, 3-(4-diethylaminophenyl)-3-(1-ethyl-2-methylindol-3-yl)phthalide and 3',6'-bis(diphenylamino)spiroisobenzofuran-1(3H),9'-[9H]xanthen-3-one.
[0320] From the viewpoint of visibility of the exposed and non-exposed areas, and pattern visibility and resolution after development, the dye N is preferably a dye whose maximum absorption wavelength changes due to radicals, and more preferably a dye that develops color due to radicals.
[0321] As the pigment N, colorless crystal violet, crystal violet lactone, brilliant green or Victoria pure blue-naphthalenesulfonate is preferred.
[0322] The dye N contained in the photosensitive layer may be one kind or two or more kinds.
[0323] From the viewpoint of visibility of the exposed and non-exposed parts, and visibility and resolution of the pattern after development, the content of the pigment N is preferably 0.1% by mass or more, more preferably 0.1% by mass to 10% by mass, further preferably 0.1% by mass to 5% by mass, and particularly preferably 0.1% by mass to 1% by mass, relative to the total mass of the photosensitive layer.
[0324] The content of the dye N refers to the content of the dye when all the dye N contained in the total mass of the photosensitive layer is in a colored state. Hereinafter, a quantitative method of the content of the dye N will be described using a dye that develops color by radicals as an example.
[0325] A solution was prepared by dissolving 0.001 g and 0.01 g of the pigment in 100 mL of methyl ethyl ketone. A photoradical polymerization initiator Irgacure OXE01 (trade name: BASF Japan Ltd.) was added to each of the obtained solutions, and irradiated with 365 nm light to generate free radicals and make all the pigments in a color-developing state. Then, in an atmospheric environment, a spectrophotometer (UV3100, manufactured by Shimadzu Corporation) was used to measure the absorbance of each solution at a liquid temperature of 25° C., and a calibration curve was prepared.
[0326] Next, the absorbance of the solution containing the photosensitive layer was measured in the same manner as above except that the photosensitive layer 3g was dissolved in methyl ethyl ketone instead of the pigment. The content of the pigment contained in the photosensitive layer was calculated from the absorbance of the solution containing the photosensitive layer obtained according to the calibration curve.
[0327] In addition, the photosensitive layer 3g is the same as the total solid content 3g in the photosensitive composition.
[0328] <Thermal crosslinking compound>
[0329] When the photosensitive layer is a negative photosensitive layer, the photosensitive layer preferably contains a thermal crosslinking compound from the viewpoint of the strength of the obtained cured film and the adhesion of the obtained uncured film. In addition, in the present invention, the thermal crosslinking compound having an ethylenically unsaturated group described later is not treated as a polymerizable compound, but as a thermal crosslinking compound.
[0330] Examples of the heat-crosslinkable compound include epoxy compounds, oxetane compounds, methylol compounds, and blocked isocyanate compounds, of which blocked isocyanate compounds are preferred from the viewpoint of the strength of the obtained cured film and the adhesion of the obtained uncured film.
[0331] The blocked isocyanate compound reacts with a hydroxyl group and a carboxyl group. Therefore, when, for example, a resin and / or a polymerizable compound has at least one of a hydroxyl group and a carboxyl group, the hydrophilicity of the formed film decreases, and there is a tendency for the function of the film formed by curing the negative photosensitive layer to be enhanced when used as a protective film.
[0332] The blocked isocyanate compound refers to a "compound having a structure in which the isocyanate group of isocyanate is protected (so-called masked) by a blocking agent".
[0333] The dissociation temperature of the blocked isocyanate compound is not particularly limited, but is preferably 100°C to 160°C, more preferably 130 to 150°C.
[0334] The dissociation temperature of the blocked isocyanate refers to "the temperature of the endothermic peak accompanying the deprotection reaction of the blocked isocyanate when measured by DSC (Differential scanning calorimetry) analysis using a differential scanning calorimeter".
[0335] As the differential scanning calorimeter, for example, a differential scanning calorimeter (model: DSC6200) manufactured by Seiko Instruments Inc. can be preferably used. However, the differential scanning calorimeter is not limited to this.
[0336] Examples of the end-capping agent having a dissociation temperature of 100 to 160°C include active methylene compounds [malonic acid diesters (dimethyl malonate, diethyl malonate, di-n-butyl malonate, di-2-ethylhexyl malonate, etc.)] and oxime compounds (formaldehyde oxime, acetaldehyde oxime, acetone oxime, methyl ethyl ketone oxime, cyclohexanone oxime, etc., compounds having a structure represented by -C(=N-OH)- in the molecule).
[0337] Among them, as the blocking agent having a dissociation temperature of 100 to 160° C., for example, at least one selected from oxime compounds is preferred from the viewpoint of storage stability.
[0338] For example, from the viewpoint of improving the brittleness of the film, improving the adhesion to the transfer target, and the like, the blocked isocyanate compound preferably has an isocyanurate structure.
[0339] The blocked isocyanate compound having an isocyanurate structure can be obtained, for example, by isocyanurating hexamethylene diisocyanate to protect it.
[0340] Among blocked isocyanate compounds having an isocyanurate structure, compounds having an oxime structure using an oxime compound as a blocking agent are preferred from the viewpoint that the dissociation temperature can be easily set within a preferred range and development residue can be easily reduced compared to compounds not having an oxime structure.
[0341] The blocked isocyanate compound may have a polymerizable group.
[0342] The polymerizable group is not particularly limited, and a known polymerizable group can be used, but a radical polymerizable group is preferred.
[0343] Examples of the polymerizable group include ethylenically unsaturated groups such as a (meth)acryloyl group, a (meth)acrylamide group, and a styryl group, and groups having an epoxy group such as a glycidyl group.
[0344] Among these, as the polymerizable group, an ethylenically unsaturated group is preferred, a (meth)acryloyl group is more preferred, and an acryloyl group is further preferred.
[0345] As the blocked isocyanate compound, a commercially available product can be used.
[0346] Examples of commercially available blocked isocyanate compounds include Karenz (registered trademark) AOI-BM, Karenz (registered trademark) MOI-BM, Karenz (registered trademark) MOI-BP, etc. (all manufactured by SHOWA DENKO KK), and blocked Duranate series (for example, Duranate (registered trademark) TPA-B80E, Duranate (registered trademark) WT32-B75P, etc., manufactured by Asahi Kasei Chemicals Corporation).
[0347] Furthermore, as the blocked isocyanate compound, compounds having the following structures can also be used.
[0348] [Chemical formula 2]
[0349]
[0350] The thermally crosslinkable compound contained in the photosensitive layer may be one kind or two or more kinds.
[0351] When the photosensitive layer contains a thermally crosslinkable compound, the content of the thermally crosslinkable compound is preferably 1% by mass to 50% by mass, and more preferably 5% by mass to 30% by mass, relative to the total mass of the photosensitive layer.
[0352] <Surfactant>
[0353] From the viewpoint of thickness uniformity, the photosensitive layer preferably contains a surfactant.
[0354] Examples of the surfactant include surfactants described in paragraph
[0017] of Japanese Patent No. 4502784 and paragraphs
[0060] to
[0071] of Japanese Unexamined Patent Application Publication No. 2009-237362.
[0355] As the surfactant, hydrocarbon surfactants, fluorine surfactants or silicone surfactants can be cited. From the viewpoint of improving environmental suitability, the surfactant preferably does not contain fluorine atoms. As the surfactant, hydrocarbon surfactants or silicone surfactants are preferred.
[0356] Examples of commercially available fluorine-based surfactants include MEGAFACE F-171, F-172, F-173, F-176, F-177, F-141, F-142, F-143, F-144, F-437, F-475, F-477, F-479, F-482, F-551-A, F-552, F-554, F-555-A, F-556, F-557, F-558, F-559, F-560, F-561, F-565, F-563, F-568, F-575, F-780, EXP. MFS-330, EXP.MFS-578, EXP.MFS-578-2, EXP.MFS-579, EXP.MFS-586, EXP.MFS-587, EXP.MFS-628, EXP.MFS-6 31. EXP.MFS-603, R-41, R-41-LM, R-01, R-40, R-40-LM, RS-43, TF-1956, RS-90, R-94, RS-72-K, DS-21 (the above is DIC Corporation), Fluorad FC430, FC431, FC171 (all manufactured by Sumitomo 3M Limited), Surflon S-382, SC-101, SC-103, SC-104, SC-105, SC-1068, SC-381, SC-383, S-393, KH-40 (all manufactured by AGC Inc.), PolyFox PF636, PF656, PF6320, PF6520, PF7002 (all manufactured by OMNOVA Solutions Inc.), Ftergent 710FL, 710FM, 610FM, 601AD, 601ADH2, 602A, 215M, 245F, 251, 212M, 250, 209F, 222F, 208G, 710LA, 710FS, 730LM, 650AC, 681, 683 (all manufactured by NEOS COMPANY LIMITED), U-120E (UNICHEM CO., LTD.), etc.
[0357] In addition, the fluorine-based surfactant can also preferably use an acrylic compound, which has a molecular structure containing a functional group containing a fluorine atom, and when heat is applied, the functional group containing a fluorine atom is partially cut off, so that the fluorine atom volatilizes. As such a fluorine-based surfactant, the MEGAFACE DS series manufactured by DIC Corporation (Chemical Industry Daily (February 22, 2016), Nikkei Industry News (February 23, 2016)) can be cited, such as MEGAFACE DS-21.
[0358] Furthermore, as the fluorine-based surfactant, it is also preferable to use a polymer of a fluorine-containing vinyl ether compound having a fluorinated alkyl group or a fluorinated alkylene ether group and a hydrophilic vinyl ether compound.
[0359] Furthermore, as the fluorine-based surfactant, a terminal polymer can be used.
[0360] Furthermore, as the fluorine-based surfactant, a fluorine-containing polymer compound can also be preferably used, which contains a constituent unit derived from a (meth)acrylate compound having a fluorine atom and a constituent unit derived from a (meth)acrylate compound having two or more (preferably five or more) alkyleneoxy groups (preferably ethyleneoxy and propyleneoxy).
[0361] Furthermore, as the fluorine-based surfactant, a fluorine-containing polymer having a group containing an ethylenically unsaturated bond in a side chain can also be used, such as MEGAFACE RS-101, RS-102, RS-718K, RS-72-K (all manufactured by DIC Corporation).
[0362] From the viewpoint of improving environmental suitability, the fluorine-based surfactant is preferably a surfactant derived from an alternative material to compounds having a linear perfluoroalkyl group having 7 or more carbon atoms, such as perfluorooctanoic acid (PFOA) and perfluorooctane sulfonic acid (PFOS).
[0363] Examples of the hydrocarbon-based surfactant include glycerin, trimethylolpropane, trimethylolethane, and ethoxylates and propoxylates thereof (e.g., glycerol propoxylate, glycerol ethoxylate, etc.), polyoxyethylene lauryl ether, polyoxyethylene stearyl ether, polyoxyethylene oleyl ether, polyoxyethylene octylphenyl ether, polyoxyethylene nonylphenyl ether, polyethylene glycol dilaurate, polyethylene glycol distearate, and sorbitan fatty acid esters.
[0364] Specific examples of hydrocarbon surfactants include Pluronic (registered trademark) L10, L31, L61, L62, 10R5, 17R2, 25R2, Tetronic 304, 701, 704, 901, 904, 150R1, HYDROPALAT WE 3323 (all manufactured by BASF), Solsperse 20000 (all manufactured by Lubrizol Japan Limited), NCW-101, NCW-1001, NCW-1002 (all manufactured by FUJIFILM Wako Pure Chemical Corporation), PIONIN D-1105, D-6112, D-6112-W, D-6315 (all manufactured by Takemoto Oil & Fat Co., Ltd.), Olfin F1010, Surfynol 104, 400, 440 (all manufactured by Nissin Chemical Co., Ltd. manufacturing) etc.
[0365] Examples of silicone surfactants include linear polymers composed of siloxane bonds, modified siloxane polymers having an organic group introduced into a side chain or a terminal, and polymers containing a structural unit having a hydrophilic group in a side chain and a structural unit having a group containing a siloxane bond in a side chain.
[0366] Among them, the silicone-based surfactant is preferably a polymer containing a structural unit having a hydrophilic group in a side chain and a structural unit having a group containing a siloxane bond in a side chain. The polymer may be a random copolymer or a block copolymer.
[0367] Examples of the structural unit having a hydrophilic group in a side chain include structural units based on the following monomers.
[0368] [Chemical formula 3]
[0369]
[0370] R 4 is a hydrogen atom or a methyl group,
[0371] R 5 is a hydrogen atom or a methyl group,
[0372] n is an integer from 1 to 4,
[0373] m is an integer from 1 to 100.
[0374] Examples of the structural unit having a siloxane bond-containing group in a side chain include structural units based on the following monomers.
[0375] [Chemical formula 4]
[0376]
[0377] R is independently an alkyl group having 1 to 3 carbon atoms,
[0378] R 1 is a hydrogen atom or a methyl group,
[0379] L 1 It is a divalent organic group or a single bond.
[0380] Examples of the structural unit having a siloxane bond-containing group in a side chain include structural units based on the following monomers.
[0381] [Chemical formula 5]
[0382]
[0383] R 1 is a hydrogen atom or a methyl group,
[0384] R 2 is an alkylene group having 1 to 10 carbon atoms,
[0385] R 3 is an alkyl group having 1 to 4 carbon atoms,
[0386] n is an integer of 5-50.
[0387] Specific examples of silicone-based surfactants include the following:
[0388] EXP.S-309-2, EXP.S-315, EXP.S-503-2, EXP.S-505-2 (all manufactured by DIC Corporation);
[0389] DOWSIL 8032ADDITIVE, Toray Silicone DC3PA, Toray Silicone SH7PA, ToraySilicone DC11PA, Toray Silicone SH21PA, Toray Silicone SH28PA, Toray SiliconeSH29PA, Toray Silicone SH30PA, Toray Silicone SH8400 (the above are manufactured by Dow Corning TorayCo., Ltd.);
[0390] X-22-4952, , X-22-6191, KP-109, KP-109, KP-112, KP-120, KP-121, KP-124, KP-125, KP-301, KP-306, KP-310, KP-322, KP -323, KP-327, KP-341, KP-368, KP-369, KP-611, KP-620, KP-621, KP-626, KP-652 (the above are Shin-Etsu Chemical Co., Ltd.);
[0391] F-4440, TSF-4300, TSF-4445, TSF-4460, TSF-4452 (all manufactured by Momentive Performance Materials Inc.); and
[0392] BYK300, BYK306, BYK307, BYK310, BYK320, BYK323, BYK325, BYK330, BYK313, BYK315N, BYK331, BYK333, BYK345, BYK347, BYK348, BYK349, BYK370, BYK377, BYK378, BYK323 (all manufactured by BYK Chemie), etc.
[0394] Furthermore, as the surfactant, a nonionic surfactant is preferred.
[0395] The surfactant contained in the photosensitive layer may be one kind or two or more kinds.
[0396] When the photosensitive layer contains a surfactant, the content of the surfactant is preferably 0.01 to 3.0% by mass, more preferably 0.01 to 1.0% by mass, and further preferably 0.05 to 0.80% by mass, relative to the total mass of the photosensitive layer.
[0397] <Other additives>
[0398] The photosensitive layer may contain known additives in addition to the above-mentioned components as necessary.
[0399] Examples of the additives include radical inhibitors, chain transfer agents, sensitizers, plasticizers, heterocyclic compounds (such as triazole), benzotriazoles, carboxybenzotriazoles, pyridines (such as isonicotinamide), and purine bases (such as adenine).
[0400] The additives contained in the photosensitive layer may be one kind or two or more kinds.
[0401] The photosensitive layer may contain a radical inhibitor.
[0402] As free radical inhibitors, for example, thermal polymerization inhibitors described in paragraph
[0018] of Japanese Patent Gazette No. 4502784 can be cited. Among them, phenothiazine, phenoxazine or 4-methoxyphenol are preferred. As other free radical inhibitors, naphthylamine, copper (I) chloride, N-nitrosophenylhydroxylamine aluminum salt and diphenylnitrosoamine can be cited. In order not to damage the sensitivity of the photosensitive layer, N-nitrosophenylhydroxylamine aluminum salt is preferred.
[0403] When the photosensitive layer contains a polymerization inhibitor, the content of the polymerization inhibitor is preferably 0.001% by mass to 5.0% by mass, more preferably 0.01% by mass to 3.0% by mass, and further preferably 0.02% by mass to 2.0% by mass relative to the total mass of the photosensitive layer. The content of the polymerization inhibitor is preferably 0.005% by mass to 5.0% by mass, more preferably 0.01% by mass to 3.0% by mass, and further preferably 0.01% by mass to 1.0% by mass relative to the total mass of the polymerizable compound.
[0404] Examples of the benzotriazoles include 1,2,3-benzotriazole, 1-chloro-1,2,3-benzotriazole, bis(N-2-ethylhexyl)aminomethylene-1,2,3-benzotriazole, bis(N-2-ethylhexyl)aminomethylene-1,2,3-tolyltriazole, and bis(N-2-hydroxyethyl)aminomethylene-1,2,3-benzotriazole.
[0405] Examples of the carboxybenzotriazoles include 4-carboxy-1,2,3-benzotriazole, 5-carboxy-1,2,3-benzotriazole, N-(N,N-di-2-ethylhexyl)aminomethylenecarboxybenzotriazole, N-(N,N-di-2-hydroxyethyl)aminomethylenecarboxybenzotriazole, and N-(N,N-di-2-ethylhexyl)aminoethylenecarboxybenzotriazole. Examples of the carboxybenzotriazoles include commercially available products such as CBT-1 (trade name: JOHOKU CHEMICAL CO., LTD.).
[0406] The total content of benzotriazoles and carboxybenzotriazoles is preferably 0.01% to 3% by mass, more preferably 0.05% to 1% by mass, relative to the total mass of the photosensitive layer. When the content is 0.01% by mass or more, the storage stability of the photosensitive layer is more excellent. On the other hand, when the content is 3% by mass or less, the maintenance of sensitivity and the suppression of dye decolorization are more excellent.
[0407] The photosensitive layer may contain a sensitizer.
[0408] The sensitizer is not particularly limited, and known sensitizers, dyes and pigments can be used. Examples of the sensitizer include dialkylaminobenzophenone compounds, pyrazoline compounds, anthracene compounds, coumarin compounds, xanthone compounds, thioxanthone compounds, acridone compounds, oxazole compounds, benzoxazole compounds, thiazole compounds, benzothiazole compounds, triazole compounds (e.g., 1,2,4-triazole), stilbene compounds, triazine compounds, thiophene compounds, naphthalimide compounds, triarylamine compounds and aminoacridine compounds.
[0409] The sensitizer contained in the photosensitive layer may be one kind or two or more kinds.
[0410] When the photosensitive layer contains a sensitizer, the content of the sensitizer can be appropriately selected according to the purpose, but from the viewpoint of improving the sensitivity to the light source and improving the curing speed by balancing the polymerization rate and chain transfer, it is preferably 0.01% by mass to 5% by mass, and more preferably 0.05% by mass to 1% by mass, relative to the total mass of the photosensitive layer.
[0411] The photosensitive layer may contain at least one selected from a plasticizer and a heterocyclic compound.
[0412] Examples of the plasticizer and the heterocyclic compound include compounds described in paragraphs
[0097] to
[0103] and paragraphs
[0111] to
[0118] of International Publication No. 2018 / 179640.
[0413] Furthermore, the photosensitive layer may further contain known additives such as metal oxide particles, antioxidants, dispersants, acid multipliers, development accelerators, conductive fibers, ultraviolet absorbers, thickeners, crosslinking agents, and organic or inorganic precipitation inhibitors.
[0414] Additives contained in the photosensitive layer are described in paragraphs
[0165] to
[0184] of Japanese Patent Application Laid-Open No. 2014-085643, and the contents of this publication are incorporated into this specification.
[0415] The thickness of the photosensitive layer is generally 0.1 μm to 300 μm, preferably 0.2 μm to 100 μm, more preferably 0.5 μm to 50 μm, further preferably 0.5 μm to 15 μm, particularly preferably 0.5 μm to 10 μm, and most preferably 0.5 μm to 8 μm. This can improve the developability of the photosensitive layer and improve the resolution.
[0416] Furthermore, in one embodiment, the thickness is preferably 0.5 μm to 5 μm, more preferably 0.5 μm to 4 μm, and even more preferably 0.5 μm to 3 μm.
[0417] Furthermore, from the viewpoint of better adhesion, the transmittance of the photosensitive layer for light of wavelength 365 nm is preferably 10% or more, more preferably 30% or more, and further preferably 50% or more. The upper limit is not particularly limited, but is preferably 99.9% or less.
[0418] <Impurities, etc.>
[0419] The photosensitive layer may contain a predetermined amount of impurities.
[0420] As specific examples of impurities, sodium, potassium, magnesium, calcium, iron, manganese, copper, aluminum, titanium, chromium, cobalt, nickel, zinc, tin, halogen and ions thereof can be cited. Among them, halide ions, sodium ions and potassium ions are easily mixed in as impurities, so it is preferably set to the following content.
[0421] The content of impurities in the photosensitive layer is preferably 80 ppm or less, more preferably 10 ppm or less, and further preferably 2 ppm or less, based on mass. The content of impurities can be 1 ppb or more, and can also be 0.1 ppm or more, based on mass.
[0422] As a method for setting the impurity content within the above range, there are exemplified the following methods: selecting a material with a small impurity content as a raw material of the composition, preventing the impurities from being mixed in during the preparation of the photosensitive layer, and removing the impurities by washing. By these methods, the impurity content can be set within the above range.
[0423] Impurities can be quantified by a known method such as ICP (Inductively Coupled Plasma) emission spectrometry, atomic absorption spectrometry, and ion chromatography.
[0424] The content of compounds such as benzene, formaldehyde, trichloroethylene, 1,3-butadiene, carbon tetrachloride, chloroform, N,N-dimethylformamide, N,N-dimethylacetamide and hexane in the photosensitive layer is preferably small. The content of these compounds relative to the total mass of the photosensitive layer is preferably 100 ppm or less, more preferably 20 ppm or less, and further preferably 4 ppm or less on a mass basis.
[0425] The lower limit of the content is preferably 10 ppb, more preferably 100 ppb, based on the total mass of the photosensitive layer. The content of these compounds can be suppressed by the same method as the above-mentioned metal impurities. Furthermore, they can be quantified by a known determination method.
[0426] In the photosensitive layer, from the viewpoint of improving the sensitivity of the photosensitive layer, the content of water relative to the total amount of the photosensitive layer is preferably 0.1% by mass or more, more preferably 0.15% by mass or more, and further preferably 0.3% by mass or more. The upper limit of the water content is not particularly limited, for example, 1.0% by mass.
[0427] The water content in the photosensitive layer was measured by the same method as that for the water content in the transfer layer.
[0428] In the photosensitive layer, if the developability is good, residues are less likely to remain on the pattern, and if the adhesion to the substrate is good, a finer pattern can be formed. From the viewpoint of improving the developability and the adhesion to the substrate, the content of iron atoms in the transfer layer is preferably 0.01 ppm to 10.0 ppm, more preferably 0.1 ppm to 10 ppm, and further preferably 0.2 ppm to 10 ppm based on the mass of the total amount of the photosensitive layer.
[0429] The content of iron atoms in the photosensitive layer was measured by the same method as that for the content of iron atoms in the transfer layer.
[0430] <Pigment>
[0431] The photosensitive layer may be a colored resin layer containing a pigment.
[0432] In recent years, a cover glass having a black frame-shaped light-shielding layer formed on the back edge of a transparent glass substrate etc. is sometimes installed on a liquid crystal display window of an electronic device to protect the liquid crystal display window. To form such a light-shielding layer, a colored resin layer can be used.
[0433] The pigment may be appropriately selected according to the desired hue, and may be selected from black pigments, white pigments, and color pigments other than black and white. Among them, when forming a black pattern, it is preferred to select a black pigment as the pigment.
[0434] As black pigment, as long as it is within the scope of not damaging the effect of the present invention, known black pigment (organic pigment or inorganic pigment, etc.) can be appropriately selected. Among them, from the viewpoint of optical density, as black pigment, for example, carbon black, titanium oxide, titanium carbide, iron oxide and graphite can be preferably cited, and carbon black is particularly preferred. As carbon black, from the viewpoint of surface resistance, at least a portion of the surface is preferably carbon black coated with resin.
[0435] From the viewpoint of dispersion stability, the particle diameter of the black pigment is preferably 0.001 μm to 0.1 μm, and more preferably 0.01 μm to 0.08 μm in terms of number average particle diameter.
[0436] Here, the particle size refers to the diameter of a circle obtained by calculating the area of the pigment particles based on a photographic image of the pigment particles taken with an electron microscope and taking into account a circle with the same area as the area of the pigment particles, and the number average particle size is the average value obtained by calculating the above-mentioned particle size for any 100 particles and averaging the 100 particle sizes calculated.
[0437] As pigments other than black pigments, white pigments described in paragraphs
[0015] and
[0114] of Japanese Patent Publication No. 2005-007765 can be used. Specifically, among white pigments, titanium oxide, zinc oxide, lithopone, light calcium carbonate, white carbon, aluminum oxide, aluminum hydroxide or barium sulfate are preferred as inorganic pigments, titanium oxide or zinc oxide are more preferred, and titanium oxide is further preferred. As inorganic pigments, rutile or anatase titanium oxide is further preferred, and rutile titanium oxide is particularly preferred.
[0438] Furthermore, the surface of titanium oxide may be treated with silicon dioxide, aluminum oxide, titanium dioxide, zirconium dioxide or organic matter, or may be treated with two or more of these treatments, thereby suppressing the catalytic activity of titanium oxide and improving heat resistance and delustering properties.
[0439] From the viewpoint of reducing the thickness of the photosensitive layer after heating, the surface treatment of the titanium oxide surface is preferably at least one of an alumina treatment and a zirconia treatment, and particularly preferably both an alumina treatment and a zirconia treatment.
[0440] Furthermore, when the photosensitive layer is a colored resin layer, the photosensitive layer preferably further comprises a color pigment other than a black pigment and a white pigment from the viewpoint of transferability. When the color pigment is included, the particle size of the color pigment is preferably 0.1 μm or less, and more preferably 0.08 μm or less from the viewpoint of better dispersibility.
[0441] Examples of the color pigment include Victoria Blue BO (Color Index (hereinafter referred to as CI) 42595), golden amine (CI41000), fat black HB (CI26150), monolight yellow GT (CI Pigment Yellow 12), permanent yellow GR (CI Pigment Yellow 17), permanent yellow HR (CI Pigment Yellow 83), permanent carmine FBB (CI Pigment Red 146), hostaperm red ESB (CI Pigment Violet 19), permanent ruby FBH (CI Pigment Red 11), pastel pink B supura (CI Pigment Red 81), Monastral fast blue (CI Pigment Red 83), and saturated fatty acid esters. blue) (CI Pigment Blue 15), Monolight Fast Black B (CI Pigment Black 1) and Carbon, CI Pigment Red 97, CI Pigment Red 122, CI Pigment Red 149, CI Pigment Red 168, CI Pigment Red 177, CI Pigment Red 180, CI Pigment Red 192, CI Pigment Red 215, CI Pigment Green 7, CI Pigment Blue 15:1, CI Pigment Blue 15:4, CI Pigment Blue 22, CI Pigment Blue 60, CI Pigment Blue 64 and CI Pigment Violet 23. Among them, CI Pigment Red 177 is preferred.
[0442] When the photosensitive layer contains a pigment, the content of the pigment is preferably greater than 3 mass % and less than 40 mass % relative to the total mass of the photosensitive layer, more preferably greater than 3 mass % and less than 35 mass %, further preferably greater than 5 mass % and less than 35 mass %, and particularly preferably greater than 10 mass % and less than 35 mass %.
[0443] When the photosensitive layer contains pigments other than black pigment (white pigment and color pigment), the content of the pigments other than black pigment is preferably 30% by mass or less, more preferably 1% to 20% by mass, and further preferably 3% to 15% by mass relative to the black pigment.
[0444] When the photosensitive layer contains a black pigment and is formed from a photosensitive composition, the black pigment (preferably carbon black) is preferably introduced into the photosensitive composition in the form of a pigment dispersion.
[0445] The dispersion liquid may be a dispersion liquid prepared by adding a mixture obtained by mixing a black pigment and a pigment dispersant in advance to an organic solvent (or vehicle) and dispersing it with a disperser. The pigment dispersant can be selected according to the pigment and the solvent, for example, a commercially available dispersant can be used. In addition, the vehicle refers to the medium part that disperses the pigment when the pigment dispersion liquid is prepared, which is in liquid form and contains a binder component that keeps the black pigment in a dispersed state and a solvent component (organic solvent) that dissolves and dilutes the binder component.
[0446] As dispersants, for example, urethane dispersants such as polyurethane, polycarboxylates such as polyacrylates, unsaturated polyamides, polycarboxylates, (partial) amine salts of polycarboxylates, ammonium salts of polycarboxylates, alkylamine salts of polycarboxylates, polysiloxanes, long-chain polyaminoamide phosphates, polycarboxylates containing hydroxyl groups, modified products thereof, amides formed by reaction of poly(lower alkylene imine) with polyesters having free carboxyl groups and their salts, oily dispersants, (meth) acrylic acid-styrene copolymers, (meth) acrylic acid-(meth) acrylic acid ester copolymers, styrene-maleic acid copolymers, polyvinyl alcohol, water-soluble resins or water-soluble polymer compounds such as polyvinyl pyrrolidone, polyesters, modified polyacrylates, ethylene oxide / propylene oxide addition compounds, phosphates, etc. The form of the dispersant can be selected from the items described in paragraphs
[0021] to
[0065] of Japanese Patent Application Laid-Open No. 2021-012355.
[0447] As a preferred dispersant, for example, a basic polymer dispersant can be mentioned. As a basic polymer dispersant, for example, a polymer containing nitrogen atoms can be mentioned. The nitrogen atom can be contained in the main chain of the polymer. The nitrogen atom can also be contained in the side chain of the polymer. The nitrogen atom can also be contained in the main chain and the side chain of the polymer. The basic polymer dispersant is preferably a polymer containing nitrogen atoms in the side chain. The surface of carbon black is generally acidic, so when using carbon black as a pigment, a basic polymer dispersant is particularly preferred as a dispersant.
[0448] As the polymer containing nitrogen atoms (preferably the polymer containing nitrogen atoms in the side chain), for example, a polymer containing at least one atomic group selected from primary amino group, secondary amino group, tertiary amino group, quaternary ammonium salt group and nitrogen-containing heterocyclic group can be cited. For example, a polymer containing quaternary ammonium salt group is preferred. The atomic group is preferably introduced into the side chain of the polymer. For example, a polymer containing at least one atomic group selected from primary amino group, secondary amino group, amino group, quaternary ammonium salt group and nitrogen-containing heterocyclic group is preferred in the side chain, and a polymer containing quaternary ammonium salt group is more preferred in the side chain. As the counter ion of the quaternary ammonium cation in the quaternary ammonium salt group, for example, a carboxylic acid ion can be cited. As the carboxylic acid ion, for example, aliphatic carboxylic acid ions and aromatic carboxylic acid ions can be cited.
[0449] The polymer containing nitrogen atoms (preferably a polymer containing nitrogen atoms in the side chain) is preferably a polymer containing constituent units from styrene and constituent units from maleimide derivatives, and more preferably a copolymer of styrene and maleimide derivatives. Maleimide derivatives have a structure in which at least one hydrogen atom of maleimide is substituted by a substituent. As maleimide derivatives, for example, maleimide derivatives containing at least one atomic group selected from primary amino groups, secondary amino groups, tertiary amino groups, quaternary ammonium salt groups and nitrogen-containing heterocyclic groups can be cited. Maleimide derivatives preferably contain maleimide derivatives of quaternary ammonium salt groups.
[0450] The dispersant may be a commercially available dispersant, for example, BYK-2012 (BYK JAPAN KK).
[0451] The photosensitive layer may contain a dispersing aid (also referred to as a pigment dispersing aid) in addition to the pigment. The dispersing aid may be selected from known dispersing aids.
[0452] As a dispersing aid, for example, a compound with an organic pigment residue can be cited. As an organic pigment, for example, phthalocyanine pigments, diketopyrrolopyrrole pigments, anthraquinone pigments, quinacridone pigments, dioxazine pigments, purple ring ketone pigments, perylene pigments, thiazine indigo pigments, triazine pigments, benzimidazolone pigments, indole pigments such as benzisoindole, isoindoline pigments, isoindoline ketone pigments, quinoline yellow pigments, naphthol pigments, reduction pigments, metal complex pigments, azo, disazo, polyazo and other azo pigments can be cited. The compound with an organic pigment residue can have an acidic substituent, a basic substituent or a neutral substituent. As an acidic substituent, for example, a sulfonic acid group, a carboxyl group and a phosphoric acid group can be cited. As a basic substituent, for example, a sulfonamide group and an amino group can be cited. As a neutral substituent, for example, a phenyl group and a phthalimide alkyl group can be cited. The form of the dispersing aid can be selected from the matters described in paragraphs
[0067] to
[0084] of JP-A-2021-012355.
[0453] As a preferred dispersing aid, for example, a compound having a phthalocyanine residue can be cited. Specifically, the dispersing aid is preferably a phthalocyanine pigment derivative or a salt thereof having an acidic substituent, more preferably a phthalocyanine pigment derivative or a salt thereof having at least one acidic substituent selected from a sulfonic acid group, a carboxyl group and a phosphoric acid group, and further preferably a phthalocyanine pigment derivative or a salt thereof having a sulfonic acid group. Phthalocyanine pigment derivatives are described in, for example, Japanese Patent Publication No. 2007-226161, International Publication No. 2016 / 163351, Japanese Patent Publication No. 2017-165820, and Japanese Patent Publication No. 5753266. These publications are incorporated into this specification by reference.
[0454] As dispersion machine, there is no particular restriction, for example, known dispersion machines such as kneader, roller mill, attritor, super mill, dissolver, homomixer and sand mill can be cited. In addition, it is also possible to grind mechanically and utilize friction to carry out fine grinding. About dispersion machine and fine grinding, it is possible to refer to the record of " Pigment Dictionary " (by Kunizo Asakura, first edition, Asakura Bookstore, 2000, 438 pages, 310 pages).
[0455] <<Middle Layer>>
[0456] The transfer layer preferably includes an intermediate layer between the temporary support and the photosensitive layer.
[0457] By providing the intermediate layer, mixing of components when applying a plurality of layer-forming compositions and during storage after application can be suppressed.
[0458] As the intermediate layer, a water-soluble resin layer containing a water-soluble resin is preferred.
[0459] Furthermore, an oxygen barrier layer having an oxygen barrier function described as a "separation layer" in Japanese Patent Application Laid-Open No. 5-072724 can be used as the intermediate layer. If the intermediate layer is an oxygen barrier layer, the sensitivity during exposure is improved, the time load of the exposure machine is reduced, and the productivity is improved, so it is preferred.
[0460] The oxygen barrier layer used as the intermediate layer may be appropriately selected from known layers described in the above-mentioned publications, etc. Among them, an oxygen barrier layer having low oxygen permeability and dispersible or soluble in water or an alkaline aqueous solution (a 1 mass % aqueous solution of sodium carbonate at 22° C.) is preferred.
[0461] Hereinafter, each component that may be contained in the intermediate layer will be described.
[0462] The intermediate layer preferably contains a resin.
[0463] The above-mentioned resin preferably contains a water-soluble resin as a part or the whole.
[0464] Examples of the resin that can be used as the water-soluble resin include polyvinyl alcohol resins, polyvinyl pyrrolidone resins, cellulose resins, acrylamide resins, polyethylene oxide resins, gelatin, vinyl ether resins, polyamide resins, and copolymers thereof.
[0465] Furthermore, as the water-soluble resin, a (meth)acrylic acid / vinyl compound copolymer can also be used. As the (meth)acrylic acid / vinyl compound copolymer, a (meth)acrylic acid / allyl (meth)acrylate copolymer is preferred, and a methacrylic acid / allyl methacrylate copolymer is more preferred.
[0466] When the water-soluble resin is a copolymer of (meth)acrylic acid / vinyl compound, the composition ratio (mol %) is, for example, preferably 90 / 10 to 20 / 80, and more preferably 80 / 20 to 30 / 70.
[0467] The lower limit of the weight average molecular weight of the water-soluble resin is preferably 5,000 or more, more preferably 7,000 or more, and further preferably 10,000 or more, and the upper limit is preferably 200,000 or less, more preferably 100,000 or less, and further preferably 50,000 or less.
[0468] The dispersion degree (Mw / Mn) of the water-soluble resin is preferably 1-10, more preferably 1-5.
[0469] In addition, from the viewpoint of further improving the interlayer mixing suppression capability of the intermediate layer, the resin contained in the intermediate layer is preferably a resin different from the resin contained in the layer disposed on one side of the intermediate layer and the resin contained in the layer disposed on the other side. For example, when the photosensitive layer contains polymer A and the thermoplastic resin (alkali-soluble resin) is contained in the thermoplastic resin layer, the resin contained in the intermediate layer is preferably a resin different from polymer A and the thermoplastic resin (alkali-soluble resin).
[0470] From the viewpoint of further improving the oxygen barrier property and the ability to suppress interlayer mixing, the water-soluble resin preferably contains polyvinyl alcohol, and more preferably contains both polyvinyl alcohol and polyvinyl pyrrolidone.
[0471] The water-soluble resin contained in the intermediate layer may be one kind or two or more kinds.
[0472] The content of the water-soluble resin is not particularly limited, but from the viewpoint of further improving the oxygen barrier and interlayer mixing inhibition ability, it is preferably 50% by mass or more, more preferably 70% by mass or more, more preferably 80% by mass or more, and particularly preferably 90% by mass or more relative to the total mass of the water-soluble resin layer (intermediate layer). In addition, the upper limit is not particularly limited, for example, preferably 99.9% by mass or less, and more preferably 99.8% by mass or less.
[0473] The intermediate layer may contain known additives such as a surfactant as necessary.
[0474] The surfactant contained in the intermediate layer may be one kind or two or more kinds.
[0475] The surfactant preferably includes at least one selected from a nonionic surfactant, a fluorine-based surfactant, and a silicone-based surfactant.
[0476] From the viewpoints of the releasability of the temporary support, resolution, oxygen barrier capability, defect suppression, and the like, the surfactant preferably contains a silicone-based surfactant.
[0477] Furthermore, from the viewpoint of improving the adhesion between the intermediate layer and the adjacent layer (photosensitive layer, thermoplastic resin, etc.) (hereinafter also referred to as "interlayer adhesion"), a silicone-based surfactant is also preferred.
[0478] From the viewpoints of the releasability, resolution, oxygen barrier ability, defect suppression, interlayer adhesion, etc. of the temporary support, the content of the silicone-based surfactant is preferably 60 mass % or more, preferably 80 mass % or more, preferably 95 mass % or more, and may also be 100 mass % relative to the total mass of the surfactant.
[0479] Examples of the silicone-based surfactant include linear polymers composed of siloxane bonds and modified siloxane polymers in which an organic group is introduced into at least one of a side chain and a terminal.
[0480] From the viewpoints of the releasability, resolution, oxygen barrier ability, defect suppression, interlayer adhesion, etc. of the temporary support, the content of the surfactant is preferably 0.1% to 10% by mass, more preferably 0.5% to 7% by mass, and further preferably 1% to 5% by mass relative to the total mass of the intermediate layer.
[0481] The thickness of the intermediate layer is not particularly limited, but is preferably 0.1 μm to 5 μm, and more preferably 0.5 to 3 μm. If the thickness of the water-soluble resin layer (intermediate layer) is within the above range, the oxygen barrier property will not be reduced and the interlayer mixing inhibition ability is excellent. In addition, the removal time of the intermediate layer during development can be suppressed.
[0482] <<Thermoplastic resin layer>>
[0483] The transfer layer preferably includes a thermoplastic resin layer between the temporary support and the intermediate layer. The transfer film has a thermoplastic resin layer, and the followability of the transfer film to the substrate in the lamination process of the transfer film and the substrate is improved, thereby suppressing the mixing of bubbles between the substrate and the transfer film. As a result, the adhesion with the layer adjacent to the thermoplastic resin layer (for example, the temporary support) can be ensured.
[0484] The thermoplastic resin layer contains a resin. The resin contains a thermoplastic resin as part or all of it. That is, in one embodiment, the resin of the thermoplastic resin layer is also preferably a thermoplastic resin.
[0485] <Alkali-soluble resin (thermoplastic resin)>
[0486] The thermoplastic resin is preferably an alkali-soluble resin.
[0487] Examples of the alkali-soluble resin include acrylic resins, polystyrene resins, styrene-acrylic copolymers, polyurethane resins, polyvinyl alcohol, polyvinyl formaldehyde, polyamide resins, polyester resins, polyamide resins, epoxy resins, polyacetal resins, polyhydroxystyrene resins, polyimide resins, polybenzoxazole resins, polysiloxane resins, polyethyleneimine, polyallylamine, and polyalkylene glycol.
[0488] As the alkali-soluble resin, acrylic resin is preferred from the viewpoint of developability and adhesion to an adjacent layer.
[0489] Here, the acrylic resin refers to a resin having at least one structural unit selected from the group consisting of a structural unit derived from (meth)acrylic acid, a structural unit derived from (meth)acrylate, and a structural unit derived from (meth)acrylic acid amide.
[0490] As for the acrylic resin, the total content of the structural unit derived from (meth)acrylic acid, the structural unit derived from (meth)acrylate, and the structural unit derived from (meth)acrylic acid amide is preferably 50% by mass or more based on the total mass of the acrylic resin.
[0491] The total content of the structural units derived from (meth)acrylic acid and the structural units derived from (meth)acrylate is preferably 30 to 100% by mass, more preferably 50 to 100% by mass, based on the total mass of the acrylic resin.
[0492] Furthermore, the alkali-soluble resin preferably contains at least one selected from a constituent unit derived from styrene and a constituent unit derived from a styrene derivative. Specific examples of the styrene derivative include vinyltoluene, p-methylstyrene, and p-chlorostyrene.
[0493] The total content of the structural units derived from styrene and the structural units derived from styrene derivatives in the alkali-soluble resin is preferably 5 to 60% by mass, more preferably 10 to 50% by mass, and further preferably 15 to 40% by mass, based on the total mass of the alkali-soluble resin.
[0494] In the alkali-soluble resin, the mass ratio of the content of the structural unit derived from the (meth)acrylate to the total content of the structural unit derived from styrene and the structural unit derived from the styrene derivative is preferably 0.3 to 2.5, more preferably 0.5 to 2.05, and even more preferably 0.7 to 1.75.
[0495] Furthermore, the alkali-soluble resin is preferably a polymer having an acid group.
[0496] Examples of the acid group include a carboxyl group, a sulfonic acid group, a phosphoric acid group and a phosphonic acid group, and a carboxyl group is preferred.
[0497] From the viewpoint of developability, the alkali-soluble resin is preferably an alkali-soluble resin having an acid value of 60 mgKOH / g or more, and more preferably a carboxyl group-containing acrylic resin having an acid value of 60 mgKOH / g or more.
[0498] The upper limit of the acid value of the alkali-soluble resin is not particularly limited, but is preferably 300 mgKOH / g or less, more preferably 250 mgKOH / g or less, further preferably 200 mgKOH / g or less, and particularly preferably 150 mgKOH / g or less.
[0499] The carboxyl group-containing acrylic resin having an acid value of 60 mgKOH / g or more is not particularly limited, and can be appropriately selected from known resins and used.
[0500] For example, the alkali-soluble resin as a carboxyl group-containing acrylic resin having an acid value of 60 mgKOH / g or more among the polymers described in paragraph
[0025] of JP-A-2011-095716, the carboxyl group-containing acrylic resin having an acid value of 60 mgKOH / g or more among the polymers described in paragraphs
[0033] to
[0052] of JP-A-2010-237589, and the carboxyl group-containing acrylic resin having an acid value of 60 mgKOH / g or more among the binder polymers described in paragraphs
[0053] to
[0068] of JP-A-2016-224162 can be cited.
[0501] The copolymerization ratio of the structural unit having a carboxyl group in the carboxyl group-containing acrylic resin is preferably 5 to 50% by mass, more preferably 10 to 40% by mass, and further preferably 12 to 30% by mass, based on the total mass of the acrylic resin.
[0502] As the alkali-soluble resin, an acrylic resin having a structural unit derived from (meth)acrylic acid is particularly preferred from the viewpoint of developability and adhesion to an adjacent layer.
[0503] The alkali-soluble resin may have a reactive group. As the reactive group, any group capable of addition polymerization may be used, and examples thereof include ethylenically unsaturated groups; polycondensable groups such as hydroxyl groups and carboxyl groups; and polyaddition reactive groups such as epoxy groups and (blocked) isocyanate groups.
[0504] The weight average molecular weight (Mw) of the alkali-soluble resin is preferably 1,000 or more, more preferably 10,000 to 100,000, and even more preferably 20,000 to 50,000.
[0505] The alkali-soluble resin contained in the thermoplastic resin layer may be one kind or two or more kinds.
[0506] From the viewpoint of developability and adhesion to adjacent layers, the content of the alkali-soluble resin is preferably 10% to 99% by mass, more preferably 20% to 90% by mass, further preferably 40% to 80% by mass, and particularly preferably 50% to 75% by mass, relative to the total mass of the thermoplastic resin layer.
[0507] <Pigment>
[0508] The thermoplastic resin layer preferably contains a dye (also referred to as "dye B") having a maximum absorption wavelength of 450 nm or longer in the wavelength range of 400 to 780 nm when developing color and whose maximum absorption wavelength changes due to acid, base or radical.
[0509] Preferred aspects of the dye B are the same as preferred aspects of the dye N described above, except for the points described below.
[0510] From the viewpoint of visibility and resolution of the exposed and non-exposed areas, the dye B is preferably a dye whose maximum absorption wavelength is changed by an acid or a radical, and more preferably a dye whose maximum absorption wavelength is changed by an acid.
[0511] From the viewpoint of visibility and resolution of the exposed and non-exposed areas, the thermoplastic resin layer preferably contains both a dye whose maximum absorption wavelength is changed by an acid as the dye B and a compound that generates an acid by light as described later.
[0512] The dye B contained in the thermoplastic resin layer may be one kind or two or more kinds.
[0513] From the viewpoint of visibility of the exposed and non-exposed parts, the content of the pigment B is preferably 0.2% by mass or more, more preferably 0.2% by mass to 6% by mass, further preferably 0.2% by mass to 5% by mass, and particularly preferably 0.25% by mass to 3.0% by mass, relative to the total mass of the thermoplastic resin layer.
[0514] Here, the content of the dye B refers to the content of the dye when all the dyes B contained in the thermoplastic resin layer are in a colored state. Hereinafter, a quantitative method of the content of the dye B will be described using a dye that develops color by radicals as an example.
[0515] A solution was prepared by dissolving 0.001 g and 0.01 g of the pigment in 100 mL of methyl ethyl ketone. A photoradical polymerization initiator Irgacure OXE01 (trade name, BASF Japan Ltd.) was added to each solution obtained, and irradiated with 365 nm light to generate free radicals, so that all the pigments were in a color-developing state. Then, under an atmospheric environment, a spectrophotometer (UV3100, manufactured by Shimadzu Corporation) was used to measure the absorbance of each solution at a liquid temperature of 25° C., and a calibration curve was prepared.
[0516] Next, 0.1 g of the thermoplastic resin layer was dissolved in methyl ethyl ketone instead of the pigment, and the absorbance of the solution in which the pigment was completely colored was measured in the same manner as above. The amount of pigment contained in the thermoplastic resin layer was calculated from the absorbance of the solution containing the thermoplastic resin layer obtained according to the calibration curve.
[0517] In addition, the thermoplastic resin layer 3g is the same as the solid content 3g of the composition for thermoplastic resin layer formation.
[0518] <Compounds that generate acids, bases, or free radicals when exposed to light>
[0519] The thermoplastic resin layer may contain a compound that generates an acid, a base, or a radical by light (also referred to simply as "compound C").
[0520] As the compound C, a compound that generates an acid, a base or a radical upon receiving active light such as ultraviolet light and visible light is preferred.
[0521] As the compound C, a known photoacid generator, photobase generator, and photoradical polymerization initiator (photoradical generator) can be used.
[0522] (Photoacid generator)
[0523] From the viewpoint of resolution, the thermoplastic resin layer may contain a photoacid generator.
[0524] Examples of the photoacid generator include the photocationic polymerization initiator that may be contained in the above-mentioned photosensitive layer, and preferred aspects are the same except for the points described below.
[0525] The photoacid generator preferably contains at least one compound selected from an onium salt compound and an oxime sulfonate compound from the viewpoint of sensitivity and resolution, and more preferably contains an oxime sulfonate compound from the viewpoint of sensitivity, resolution and adhesion.
[0526] Furthermore, as the photo-acid generator, a photo-acid generator having the following structure is also preferred.
[0527] [Chemical formula 6]
[0528]
[0529] (Photoradical polymerization initiator)
[0530] The thermoplastic resin layer may contain a photoradical polymerization initiator.
[0531] Examples of the photoradical polymerization initiator include the photoradical polymerization initiators that may be contained in the above-mentioned photosensitive layer, and preferred embodiments are also the same.
[0532] (Photobase Generator)
[0533] The thermoplastic resin composition may contain a photobase generator.
[0534] The photobase generator is not particularly limited as long as it is a known photobase generator, and examples thereof include 2-nitrobenzylcyclohexylcarbamate, triphenylmethanol, O-carbamoylhydroxyamide, O-carbamoyloxime, [[(2,6-dinitrobenzyl)oxy]carbonyl]cyclohexylamine, bis[[(2-nitrobenzyl)oxy]carbonyl]hexane 1,6-diamine, 4-(methylthiobenzoyl)-1-methyl-1-morpholinoethane, (4-morpholinobenzoyl)-1-benzyl-1-dimethyl Aminopropane, N-(2-nitrobenzyloxycarbonyl)pyrrolidine, hexaaminecobalt(III) tris(triphenylmethylborate), 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone, 1-(4-morpholinophenyl)-butanone manufactured by Sanyo Trading Co., Ltd., 2,6-dimethyl-3,5-diacetyl-4-(2-nitrophenyl)-1,4-dihydropyridine and 2,6-dimethyl-3,5-diacetyl-4-(2,4-dinitrophenyl)-1,4-dihydropyridine.
[0535] The compound C contained in the thermoplastic resin layer may be one kind or two or more kinds.
[0536] The content of the compound C is preferably 0.1 to 10% by mass, more preferably 0.5 to 5% by mass, based on the total mass of the thermoplastic resin layer, from the viewpoint of visibility and resolution of the exposed and non-exposed areas.
[0537] <Plasticizer>
[0538] The thermoplastic resin layer preferably contains a plasticizer from the viewpoints of resolution, adhesion to an adjacent layer, and developability.
[0539] The molecular weight of the plasticizer is preferably smaller than the molecular weight of the alkali-soluble resin (weight average molecular weight when it is an oligomer or a polymer and has a molecular weight distribution). The molecular weight (weight average molecular weight) of the plasticizer is preferably 200 to 2,000.
[0540] The plasticizer is not particularly limited as long as it is a compound that is compatible with the alkali-soluble resin and exhibits plasticity, but from the viewpoint of imparting plasticity, the plasticizer preferably has an alkyleneoxy group in the molecule, and more preferably a polyalkylene glycol compound. The alkyleneoxy group contained in the plasticizer more preferably has a polyethyleneoxy structure or a polypropyleneoxy structure.
[0541] Furthermore, from the viewpoint of resolution and storage stability, the plasticizer preferably contains a (meth)acrylate compound. From the viewpoint of compatibility, resolution, and adhesion to adjacent layers, the alkali-soluble resin is more preferably an acrylic resin and the plasticizer contains a (meth)acrylate compound.
[0542] Examples of the (meth)acrylate compound used as the plasticizer include the (meth)acrylate compounds described as the polymerizable compound contained in the above-mentioned photosensitive layer.
[0543] In the transfer film, when the thermoplastic resin layer and the photosensitive layer are directly contacted and laminated, the thermoplastic resin layer and the negative photosensitive layer preferably both contain the same (meth)acrylate compound. This is because the diffusion of components between the layers can be suppressed and the storage stability can be improved by respectively containing the same (meth)acrylate compound in the thermoplastic resin layer and the photosensitive layer.
[0544] When the thermoplastic resin layer contains a (meth)acrylate compound as a plasticizer, the (meth)acrylate compound is preferably not polymerized even in the exposed portion after exposure from the viewpoint of adhesion between the thermoplastic resin and the adjacent layer.
[0545] In addition, from the viewpoints of resolution of the thermoplastic resin layer, adhesion to adjacent layers, and developability, the (meth)acrylate compound used as a plasticizer is preferably a polyfunctional (meth)acrylate compound having two or more (meth)acryloyl groups in one molecule.
[0546] Furthermore, as the (meth)acrylate compound used as the plasticizer, a (meth)acrylate compound or a urethane (meth)acrylate compound having an acid group is also preferred.
[0547] The plasticizer contained in the thermoplastic resin layer may be one kind or two or more kinds.
[0548] From the viewpoint of resolution of the thermoplastic resin layer, adhesion to adjacent layers, and developability, the content of the plasticizer is preferably 1 to 70% by mass, more preferably 10 to 60% by mass, and even more preferably 20 to 50% by mass, based on the total mass of the thermoplastic resin layer.
[0549] <Sensitizer>
[0550] The thermoplastic resin layer may contain a sensitizer.
[0551] The sensitizer is not particularly limited, and examples thereof include the sensitizers that can be contained in the above-mentioned negative photosensitive layer.
[0552] The sensitizer contained in the thermoplastic resin layer may be one kind or two or more kinds.
[0553] The content of the sensitizer can be appropriately selected depending on the purpose, but is preferably 0.01 to 5% by mass, more preferably 0.05 to 1% by mass, based on the total mass of the thermoplastic resin layer from the viewpoint of improving sensitivity to light sources and visibility of exposed and non-exposed areas.
[0554] <Additives, etc.>
[0555] The thermoplastic resin layer may contain known additives such as a surfactant, in addition to the above-mentioned components, as necessary.
[0556] The thermoplastic resin layer is described in paragraphs
[0189] to
[0193] of Japanese Patent Application Laid-Open No. 2014-085643, and the contents described in the publication are incorporated into the present specification.
[0557] The thickness of the thermoplastic resin layer is not particularly limited, but from the viewpoint of adhesion to the adjacent layer, it is preferably 1 μm or more, more preferably 2 μm or more. The upper limit is not particularly limited, but from the viewpoint of developability and resolution, it is preferably 20 μm or less, more preferably 10 μm or less, and further preferably 8 μm or less.
[0558] <<Protective film>>
[0559] The transfer film may have a protective film.
[0560] As the protective film, a resin film having heat resistance and solvent resistance can be used, and examples thereof include polyolefin films such as polypropylene films and polyethylene films, polyester films such as polyethylene terephthalate films, polycarbonate films, and polystyrene films.
[0561] Furthermore, as the protective film, a resin film made of the same material as that of the temporary support body described above can be used.
[0562] Among them, as the protective film, a polyolefin film is preferred, a polypropylene film or a polyethylene film is more preferred, and a polyethylene film is further preferred.
[0563] The thickness of the protective film is preferably 1 μm to 100 μm, more preferably 5 μm to 50 μm, further preferably 5 μm to 40 μm, and particularly preferably 15 μm to 30 μm.
[0564] The thickness of the protective film is preferably 1 μm or more from the viewpoint of excellent mechanical strength, and is preferably 100 μm or less from the viewpoint of being relatively inexpensive.
[0565] Furthermore, in the protective film, the number of fisheyes with a diameter of 80 μm or more contained in the protective film is preferably 5 / m. 2 the following.
[0566] The "fish eyes" are particles where foreign matter, undissolved matter, oxidative degradation products, etc. of the material are taken into the film when the material is heat-melted, kneaded, extruded, biaxially stretched, cast, etc. to produce the film.
[0567] The number of particles with a diameter of 3 μm or more contained in the protective film is preferably 30 particles / mm. 2 Below, more preferably 10 / mm 2 Below, more preferably 5 / mm 2 the following.
[0568] This can suppress defects caused by the transfer of the unevenness caused by the particles contained in the protective film to the photosensitive layer or the conductive layer.
[0569] From the viewpoint of providing windability, the arithmetic mean roughness Ra of the surface of the protective film on the side opposite to the surface in contact with the composition layer is preferably 0.01 μm or more, more preferably 0.02 μm or more, and further preferably 0.03 μm or more. On the other hand, it is preferably less than 0.50 μm, more preferably 0.40 μm or less, and further preferably 0.30 μm or less.
[0570] The protective film can also be a recycling product. As the recycling product, the used film can be cleaned and shredded, and the product formed by filmization as a material can be enumerated. As the specific example of the recycling product, the Ecouse series of T0RAY INDUSTRIES, INC. can be enumerated.
[0571] From the viewpoint of suppressing defects during transfer, the surface roughness Ra of the surface of the protective film in contact with the composition layer is preferably 0.01 μm or more, more preferably 0.02 μm or more, and further preferably 0.03 μm or more. On the other hand, it is preferably less than 0.50 μm, more preferably 0.40 μm or less, and further preferably 0.30 μm or less.
[0572] <<Method for producing transfer film>>
[0573] The method for producing the transfer film according to the present invention is not particularly limited, and a known method can be used.
[0574] As a method for manufacturing the above-mentioned transfer film 20, for example, there can be cited a method comprising the following steps: applying a thermoplastic resin layer forming composition on the surface of a temporary support 11 to form a coating film, and then drying the coating film to form a thermoplastic resin layer 13; applying an intermediate layer forming composition on the surface of the thermoplastic resin layer 13 to form a coating film, and then drying the coating film to form an intermediate layer 15; applying a photosensitive composition on the surface of the intermediate layer 15 to form a coating film, and then drying the coating film to form a photosensitive layer 17.
[0575] The protective film 19 is pressure-bonded onto the photosensitive layer 17 of the laminated body produced by the above-described production method, thereby producing the transfer film 20 .
[0576] As a method for producing a transfer film according to the present invention, it is preferred to produce a transfer film 20 including a temporary support 11, a thermoplastic resin layer 13, an intermediate layer 15, a photosensitive layer 17, and a protective film 19 by including a step of providing a protective film 19 in contact with a surface of the photosensitive layer 17 on the side opposite to the side having the temporary support 11. The thermoplastic resin layer 13, the intermediate layer 15, and the photosensitive layer 17 correspond to the transfer layer 12.
[0577] After the transfer film 20 is manufactured by the above-mentioned manufacturing method, a transfer film in roll form can be produced and stored by winding up the transfer film 20. The transfer film in roll form can be provided as it is to the roll-to-roll bonding process to be described later.
[0578] Furthermore, as a method for producing the transfer film 20 described above, a method of forming the thermoplastic resin layer 13 on the surface of the intermediate layer 15 after forming the photosensitive layer 17 and the intermediate layer 15 on the protective film 19 may be adopted.
[0579] <Method for Forming Thermoplastic Resin Layer>
[0580] The method for forming the thermoplastic resin layer on the temporary support is not particularly limited, and a known method can be used. For example, the thermoplastic resin layer can be formed by applying a thermoplastic resin layer-forming composition on the temporary support and then drying it as necessary.
[0581] As the composition for forming the thermoplastic resin layer, it is preferred to contain various components and a solvent for forming the above-mentioned thermoplastic resin layer. In addition, in the composition for forming the thermoplastic resin layer, the preferred range of the content of each component relative to the total solid content of the composition is the same as the preferred range of the content of each component relative to the total mass of the above-mentioned thermoplastic resin layer.
[0582] The solvent is not particularly limited as long as it can dissolve or disperse the components other than the solvent, and a known solvent can be used. Examples of the solvent include the same solvents as those contained in the photosensitive composition described later, and preferred embodiments are also the same.
[0583] The content of the solvent is preferably 50 to 1,900 parts by mass, more preferably 100 to 900 parts by mass, based on 100 parts by mass of the total solid content of the thermoplastic resin layer-forming composition.
[0584] The method for forming the thermoplastic resin layer is not particularly limited as long as it is a method that can form a layer containing the above-mentioned components, and examples thereof include known coating methods (slit coating, spin coating, curtain coating, inkjet coating, etc.).
[0585] <Method for Forming Intermediate Layer>
[0586] As the composition for forming the intermediate layer, it is preferred to include various components and solvents for forming the above-mentioned intermediate layer. In addition, in the composition for forming the intermediate layer, the preferred range of the content of each component relative to the total solid content of the composition for forming the intermediate layer is the same as the preferred range of the content of each component relative to the total mass of the above-mentioned intermediate layer.
[0587] The solvent is not particularly limited as long as it can dissolve or disperse the water-soluble resin, but is preferably at least one selected from water and a water-miscible organic solvent, and more preferably water or a mixed solvent of water and a water-miscible organic solvent.
[0588] Examples of the water-miscible organic solvent include alcohols having 1 to 3 carbon atoms, acetone, ethylene glycol, and glycerin. Alcohols having 1 to 3 carbon atoms are preferred, and methanol or ethanol is more preferred.
[0589] The solvent contained in the intermediate layer forming composition may be one kind or two or more kinds.
[0590] The content of the solvent is preferably 50 to 2,500 parts by mass, more preferably 50 to 1,900 parts by mass, and even more preferably 100 to 900 parts by mass, based on 100 parts by mass of the total solid content of the intermediate layer forming composition.
[0591] The method for forming the intermediate layer is not particularly limited as long as it is a method capable of forming a layer containing the above-mentioned components, and examples thereof include known coating methods (slit coating, spin coating, curtain coating, inkjet coating, etc.).
[0592] <Method for Forming Photosensitive Layer>
[0593] From the viewpoint of excellent productivity, it is preferably formed by a coating method using a photosensitive composition containing the components constituting the above-mentioned photosensitive layer (for example, polymer A, polymerizable compound, polymerization initiator, etc.) and a solvent.
[0594] Specifically, the method for producing the transfer film of the present invention is preferably a method in which a photosensitive composition is applied to the intermediate layer to form a coating film, and the coating film is dried at a predetermined temperature to form a photosensitive layer. In addition, the amount of residual solvent is adjusted by drying the coating film.
[0595] As the photosensitive composition, it is preferred to include various components and solvents that form the above-mentioned photosensitive layer. In addition, in the photosensitive composition, the preferred range of the content of each component relative to the total solid content of the photosensitive composition is the same as the preferred range of the content of each component relative to the total mass of the above-mentioned photosensitive layer.
[0596] The solvent is not particularly limited as long as it can dissolve or disperse the components other than the solvent, and a known solvent can be used. Specifically, for example, alkylene glycol ether solvents, alkylene glycol ether acetate solvents, alcohol solvents (methanol and ethanol, etc.), ketone solvents (acetone and methyl ethyl ketone, etc.), aromatic hydrocarbon solvents (toluene, etc.), aprotic polar solvents (N, N-dimethylformamide, etc.), cyclic ether solvents (tetrahydrofuran, etc.), ester solvents (n-propyl acetate, etc.), amide solvents, lactone solvents, and mixed solvents containing two or more of these.
[0597] The solvent preferably contains at least one selected from an alkylene glycol ether solvent and an alkylene glycol ether acetate solvent. Among them, a mixed solvent containing at least one selected from an alkylene glycol ether solvent and an alkylene glycol ether acetate solvent and at least one selected from a ketone solvent and a cyclic ether solvent is more preferred, and a mixed solvent containing at least three of at least one selected from an alkylene glycol ether solvent and an alkylene glycol ether acetate solvent, a ketone solvent, and a cyclic ether solvent is further preferred.
[0598] Examples of the alkylene glycol ether solvent include ethylene glycol monoalkyl ether, ethylene glycol dialkyl ether, propylene glycol monoalkyl ether (propylene glycol monomethyl ether acetate, etc.), propylene glycol dialkyl ether, diethylene glycol dialkyl ether, dipropylene glycol monoalkyl ether, and dipropylene glycol dialkyl ether.
[0599] Examples of the alkylene glycol ether acetate solvent include ethylene glycol monoalkyl ether acetate, propylene glycol monoalkyl ether acetate, diethylene glycol monoalkyl ether acetate, and dipropylene glycol monoalkyl ether acetate.
[0600] As the solvent, the solvents described in paragraphs
[0092] to
[0094] of International Publication No. 2018 / 179640 and the solvents described in paragraph
[0014] of Japanese Patent Application Laid-Open No. 2018-177889 can be used, and these contents are incorporated into this specification.
[0601] The solvent contained in the photosensitive composition may be one kind or two or more kinds.
[0602] The content of the solvent is preferably 50 to 1,900 parts by mass, more preferably 100 to 1,200 parts by mass, and even more preferably 100 to 900 parts by mass, based on 100 parts by mass of the total solid content of the composition.
[0603] Examples of a method for coating the photosensitive composition include a printing method, a spray coating method, a roll coating method, a bar coating method, a curtain coating method, a spin coating method, and a die coating method (ie, a slit coating method).
[0604] As a method for drying the coating film of the photosensitive composition, heating drying and reduced pressure drying are preferred.
[0605] The drying temperature is preferably 80° C. or higher, more preferably 90° C. or higher. The upper limit thereof is preferably 130° C. or lower, more preferably 120° C. or lower. Drying can also be performed while continuously changing the temperature.
[0606] The drying time is preferably 20 seconds or longer, more preferably 40 seconds or longer, and even more preferably 60 seconds or longer. The upper limit is not particularly limited, but is preferably 600 seconds or shorter, and more preferably 300 seconds or shorter.
[0607] Moreover, by bonding the protective film to the photosensitive layer, the transfer film according to the present invention can be produced.
[0608] The method of bonding the protective film to the photosensitive layer is not particularly limited, and a known method may be used.
[0609] As an apparatus for bonding the protective film to the photosensitive layer, a known laminator such as a vacuum laminator and an automatic cutting laminator can be mentioned.
[0610] The laminator is preferably equipped with any heatable roller such as a rubber roller and is a device capable of applying pressure and heat.
[0611] The transfer film according to the present invention can be applied to various uses.
[0612] The transfer film according to the present invention can be suitably used for, for example, electrode protection films, insulating films, planarization films, overcoat films, hard coating films, passivation films, partition walls, spacers, microlenses, optical filters, antireflection films, etching resists, and plated parts.
[0613] More specifically, the transfer film involved in the present invention can be applied to a protective film or insulating film for touch panel electrodes, a protective film or insulating film for a printed wiring board, a protective film or insulating film for a TFT substrate, a color filter, a protective film for a color filter, an etching photoresist for forming wiring, a plating photoresist for forming wiring, and a plating photoresist for forming a flexible printed wiring board.
[0614] [Method for forming a conductor pattern]
[0615] The method for forming a pattern according to the present invention comprises the following steps:
[0616] preparing a transfer film including a temporary support and a transfer layer disposed on the temporary support (preparation step);
[0617] laminating the transfer film and the substrate in such a manner that a surface of the transfer film opposite to the surface of the temporary support is in contact with the substrate (laminating step);
[0618] Peeling off the temporary support to obtain a laminate (temporary support peeling step);
[0619] exposing the laminate in a pattern (exposure step); and
[0620] The exposed laminate is developed to form a pattern.
[0621] Among them, the thermal deformation rate of the temporary support is preferably 1.0% or less.
[0622] Hereinafter, each step will be described.
[0623] 〔Preparation process〕
[0624] In the preparation step, a transfer film including a temporary support and a transfer layer disposed on the temporary support is prepared. Preferred embodiments of the transfer film are as described above.
[0625] 〔Lamination process〕
[0626] In the bonding step, the transfer film and the substrate are bonded together so that the surface of the transfer film opposite to the surface of the temporary support comes into contact with the substrate.
[0627] When the transfer film includes a protective film, the protective film is peeled off and then the transfer film is bonded to the substrate.
[0628] The transfer film is preferably laminated to the substrate by overlaying the substrate on the transfer layer and applying pressure and heat using rollers, etc. A known laminator such as a laminator, a vacuum laminator, and an automatic cutting laminator that can further improve productivity can be used for lamination.
[0629] The lamination temperature is preferably 70°C to 130°C.
[0630] <Substrate>
[0631] As the substrate used for forming the pattern according to the present invention, a known substrate can be used. The substrate may be a substrate having a conductive layer, or may be a substrate having a conductive layer on the surface of a base material.
[0632] The substrate may have any layer other than the conductive layer as necessary.
[0633] Examples of the base material constituting the substrate include glass, silicon, and resin films.
[0634] When glass is used as the substrate, the substrate is preferably transparent and has a refractive index of 1.50 to 1.52.
[0635] Examples of the transparent glass substrate include tempered glass represented by Gorilla Glass from Corning Incorporated Co., Ltd. Also, materials described in Japanese Patent Application Laid-Open Nos. 2010-86684, 2010-152809, and 2010-257492 can be used as the transparent glass substrate.
[0636] When a resin film is used as the substrate, the substrate is preferably a resin film with small optical distortion and / or high transparency. Examples of such resin films include polyethylene terephthalate (PET) films, polyethylene naphthalate films, polycarbonate films, triacetyl cellulose films, and cycloolefin polymer films.
[0637] When the circuit wiring for a touch panel is manufactured by a roll-to-roll method, the substrate is preferably a resin film. Furthermore, when the circuit wiring for a touch panel is manufactured by a roll-to-roll method, the substrate is preferably a resin sheet.
[0638] The thickness of the substrate is preferably 5 μm to 200 μm, more preferably 10 μm to 100 μm.
[0639] The conductive layer is preferably at least one layer selected from a metal layer, a conductive metal oxide layer, a graphite layer, a carbon nanotube layer, and a conductive polymer layer from the viewpoint of conductivity and thin line formability.
[0640] Furthermore, the substrate may have only one conductive layer or two or more conductive layers. When two or more conductive layers are provided, the conductive layers are preferably made of different materials.
[0641] A preferred embodiment of the conductive layer is described in, for example, paragraph
[0141] of International Publication No. 2018 / 155193, the contents of which are incorporated into this specification.
[0642] The conductive layer is preferably a metal layer.
[0643] The metal layer is a layer containing a metal, and the metal is not particularly limited, and a known metal can be used. The metal layer is preferably a conductive layer.
[0644] Examples of the main component of the metal layer (so-called main metal) include copper, chromium, lead, nickel, gold, silver, tin, and zinc. The "main metal" refers to the metal with the largest content among the metals contained in the metal layer.
[0645] The thickness of the conductive layer is not particularly limited, but is preferably 50 nm or more, more preferably 100 nm or more, and the upper limit is preferably 2 μm or less.
[0646] The method for forming the conductive layer is not particularly limited, and examples thereof include a method of applying a dispersion in which metal fine particles are dispersed and sintering the coating, a sputtering method, a deposition method, and other known methods.
[0647] [Temporary support peeling step]
[0648] In the temporary support peeling step, the temporary support is peeled off to obtain a laminated body. In the pattern forming method according to the present invention, since the temporary support is peeled off in advance, foreign matter contained in the temporary support does not affect exposure in the exposure step.
[0649] The peeling method is not particularly limited, and the same cover film peeling mechanism as that described in paragraphs
[0161] to
[0162] of Japanese Patent Application Laid-Open No. 2010-072589 can be used.
[0650] [Exposure process]
[0651] In the exposure step, the laminated body obtained in the peeling step is exposed in a pattern.
[0652] The detailed configuration and specific size of the pattern in the pattern exposure are not particularly limited. At least a portion of the pattern (preferably the electrode pattern and / or lead wiring portion of the touch panel) preferably includes a fine line with a width of 20 μm or less, and more preferably includes a fine line with a width of 10 μm or less. The display quality of a display device (for example, a touch panel) having an input device having circuit wiring manufactured by the manufacturing method of the circuit wiring can be improved, and the area occupied by the lead wiring can be reduced.
[0653] The light source used for exposure is not particularly limited as long as it irradiates light of a wavelength capable of exposing the photosensitive layer (for example, 365 nm or 405 nm), and can be appropriately selected and used. Examples of the light source include ultra-high pressure mercury lamps, high pressure mercury lamps, metal halide lamps, and LEDs (Light Emitting Diodes).
[0654] The exposure dose is preferably 5 mJ / cm 2 ~200mJ / cm 2 , more preferably 10 mJ / cm 2 ~100mJ / cm 2 .
[0655] In the exposure step, the exposure may be performed after the mask is brought into contact with the photosensitive layer, or the exposure may be performed after the mask is brought close to the photosensitive layer without being brought into contact with the layer.
[0656] In addition, in the case of contact exposure, the exposure method can appropriately select and use the contact exposure method, and in the case of non-contact exposure method, a proximity exposure method, a projection exposure method of a lens system or a reflector system, or a direct exposure method using an exposure laser or the like can be appropriately selected and used. In the case of a projection exposure method of a lens system or a reflector system, an exposure machine with an appropriate lens aperture number (NA) can be used according to the required resolution and depth of focus. In the case of a direct exposure method, the photosensitive layer can be directly exposed, or the photosensitive layer can be reduced and projected through a lens. Moreover, exposure can be performed not only in the atmosphere, but also under reduced pressure or in a vacuum. Moreover, liquids such as water can be interposed between the light source and the photosensitive layer for exposure.
[0657] As the mask, for example, a quartz mask, a soda-lime glass mask and a film mask can be cited. Among them, the quartz mask is preferred from the viewpoint of excellent dimensional accuracy, and the film mask is preferred from the viewpoint of easy large-scale. As the base material of the film mask, a polyester film is preferred, and a polyethylene terephthalate film is more preferred.
[0658] As a specific example of the base material of the film mask, XPR-7S SG (manufactured by FUJIFILM Graphic Systems Co., Ltd.) can be mentioned.
[0659] Preferred aspects of the light source, exposure amount, and exposure method used for exposure are described, for example, in paragraphs
[0146] to
[0147] of International Publication No. 2018 / 155193, and these contents are incorporated into this specification.
[0660] 〔Development process〕
[0661] In the development step, the exposed laminate is developed to form a pattern.
[0662] Development can be performed using a developer.
[0663] The developer is preferably an alkaline aqueous solution. Examples of alkaline compounds that may be contained in the alkaline aqueous solution include sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, and choline (2-hydroxyethyltrimethylammonium hydroxide).
[0664] Examples of the method of development include spin immersion development, shower development, spin development, and immersion development.
[0665] Preferred developing solutions include, for example, those described in paragraph
[0194] of International Publication No. 2015 / 093271, and preferred developing methods include, for example, those described in paragraph
[0195] of International Publication No. 2015 / 093271.
[0666] [Post-exposure process and post-baking process]
[0667] The pattern forming method according to the present invention may include a step of exposing the pattern obtained in the development step (post-exposure step) and / or a step of heating the pattern (post-baking step).
[0668] When both the post-exposure step and the post-bake step are included, it is preferred that the post-bake be performed after the post-exposure step.
[0669] The exposure dose of post-exposure is preferably 100 mJ / cm 2 ~5000mJ / cm 2 , more preferably 200 mJ / cm 2 ~3000mJ / cm 2 .
[0670] The temperature of the post-baking is preferably 80°C to 250°C, more preferably 90°C to 160°C.
[0671] The post-baking time is preferably 1 minute to 180 minutes, more preferably 10 minutes to 60 minutes.
[0672] [Method for manufacturing circuit wiring]
[0673] A first aspect of the method for manufacturing a circuit wiring according to the present invention includes the following steps:
[0674] preparing a transfer film including a temporary support and a transfer layer disposed on the temporary support (preparation step);
[0675] laminating the transfer film and the substrate in such a manner that a surface of the transfer film opposite to the surface of the temporary support is in contact with the substrate (laminating step);
[0676] Peeling off the temporary support to obtain a laminate (temporary support peeling step);
[0677] exposing the laminate in a pattern (exposure step); and
[0678] developing the exposed laminate to form a pattern (development step);
[0679] Plating the substrate in an area where no pattern is arranged (plating step); and
[0680] Peeling off the pattern (pattern peeling process),
[0681] Among them, the thermal deformation rate of the temporary support is preferably 1.0% or less.
[0682] The preparation step, the bonding step, the temporary support peeling step, and the exposure step are the same as those in the pattern forming method already described, and thus description thereof will be omitted.
[0683] If the area without pattern is plated, a conductor pattern will be formed. This is generally called a semi-additive method.
[0684] 〔Plating process〕
[0685] In the plating step, a region of the substrate where no pattern is arranged is plated.
[0686] As a plating method, a well-known method can be applied, for example, electroplating and electroless plating are mentioned. The plating is preferably electroplating.
[0687] Examples of the metal contained in the plating layer include well-known metals.
[0688] Specific examples include metals such as copper, chromium, lead, nickel, gold, silver, tin, and zinc, and alloys of these metals.
[0689] Among them, from the viewpoint of further improving the conductivity of the conductive pattern, the plating layer preferably contains copper or its alloy. Also, from the viewpoint of further improving the conductivity of the conductive pattern, the plating layer preferably contains copper as a main component.
[0690] As a component of the plating solution used in electroplating, for example, a water-soluble copper salt can be mentioned. As a water-soluble copper salt, a water-soluble copper salt commonly used as a component of the plating solution can be used. As a water-soluble copper salt, for example, it is preferably selected from at least one of an inorganic copper salt, an alkanesulfonic acid copper salt, an alkanesulfonic acid copper salt and an organic acid copper salt. As an inorganic copper salt, for example, copper sulfate, copper oxide, copper chloride and copper carbonate can be mentioned. As an alkanesulfonic acid copper salt, for example, copper methanesulfonate and copper propanesulfonate can be mentioned. As an alkanesulfonic acid copper salt, for example, copper isethionate and copper propanesulfonate can be mentioned. As an organic acid copper salt, for example, copper acetate, copper citrate and copper tartrate can be mentioned.
[0691] The plating solution may contain sulfuric acid. When the plating solution contains sulfuric acid, the pH and sulfate ion concentration of the plating solution can be adjusted.
[0692] The method and conditions of electroplating are not limited. For example, the conductor pattern can be formed by supplying the laminate after the development process to a plating tank filled with a plating solution. In the electroplating, for example, the conductor pattern can be formed by controlling the current density and the conveying speed of the transparent substrate.
[0693] The temperature of the plating solution used in the electroplating is preferably 70° C. or lower, more preferably 10° C. to 40° C. The current density in the electroplating is preferably 0.1 A / dm 2 ~100A / dm 2 , more preferably 0.5A / dm 2 ~20A / dm 2 By increasing the current density, the productivity of the conductor pattern can be improved. By reducing the current density, the uniformity of the thickness of the conductor pattern can be improved.
[0694] 〔Pattern peeling process〕
[0695] The pattern peeling step is a step of peeling off the pattern.
[0696] As a method of peeling off the residual pattern, for example, a method of removing by chemical treatment can be mentioned, and a method of removing using a peeling liquid is preferred.
[0697] Examples of a method for removing the remaining pattern include a method of removing the pattern using a stripping liquid by a known method such as a spray coating method, a shower method, and a spin immersion method.
[0698] Examples of the stripping solution include a stripping solution obtained by dissolving a basic compound in at least one selected from water, dimethyl sulfoxide, and N-methylpyrrolidone.
[0699] As the alkaline compound (a compound that dissolves in water and exhibits alkalinity), for example, alkaline inorganic compounds such as sodium hydroxide and potassium hydroxide, and alkaline organic compounds such as primary amine compounds, secondary amine compounds, tertiary amine compounds, and quaternary ammonium salt compounds can be cited. As the alkaline organic compound, tetramethylammonium hydroxide or an alkanolamine compound is preferred.
[0700] The method for stripping the pattern may be a method of immersing the substrate having the residual resist pattern in a stripping solution having a liquid temperature of 30° C. to 80° C. (preferably 50° C. to 80° C.) under stirring for 1 minute to 30 minutes.
[0701] It is also preferred that the stripping liquid does not dissolve the conductive layer.
[0702] The pH of the stripping solution during the stripping treatment is preferably 11 or more, more preferably 12 or more, and further preferably 13 or more. The upper limit is preferably 14 or less, and more preferably 13.8 or less. The pH can be measured using a known pH meter in accordance with JIS Z8802-1984. The pH measurement temperature is set to 25°C.
[0703] The temperature of the stripping solution during the stripping treatment is preferably higher than the temperature of the developing solution during the developing treatment. Specifically, the value obtained by subtracting the temperature of the developing solution from the temperature of the stripping solution (temperature of the stripping solution - temperature of the developing solution) is preferably 10°C or higher, more preferably 20°C or higher. The upper limit is preferably 100°C or lower, more preferably 80°C or lower.
[0704] The pH of the stripping solution during the stripping treatment is preferably higher than the pH of the developer during the development treatment. Specifically, the value obtained by subtracting the pH of the developer from the pH of the stripping solution (pH of the stripping solution - pH of the developer) is preferably 1 or more, more preferably 1.5 or more. The upper limit is preferably 5 or less, more preferably 4 or less.
[0705] It is also preferable to perform a rinsing process to remove the stripping liquid remaining on the substrate after stripping the pattern with the stripping liquid. Water or the like can be used for the rinsing process.
[0706] After the patterned stripping and / or rinsing process using the stripping liquid, a drying process may be performed to remove excess liquid from the substrate.
[0707] In the second mode of the circuit wiring manufacturing method involved in the present invention, it is preferred to include the above-mentioned bonding process, the above-mentioned peeling process, the above-mentioned exposure process, a process of etching the substrate in an area where no pattern is configured (etching process) and a process of peeling off the pattern (pattern peeling process).
[0708] 〔Etching process〕
[0709] In the etching step, the substrate is etched using the pattern formed by the photosensitive layer as an etching resist.
[0710] As an etching treatment method, a known method can be applied, for example, the method described in paragraphs
[0209] to
[0210] of Japanese Patent Gazette No. 2017-120435, the method described in paragraphs
[0048] to
[0054] of Japanese Patent Gazette No. 2010-152155, a wet etching method by immersion in an etching solution, and a dry etching method based on plasma etching or the like.
[0711] The etching solution used for wet etching may be an acidic or alkaline etching solution appropriately selected according to the object to be etched.
[0712] Examples of the acidic etching solution include aqueous solutions of an acidic component selected from hydrochloric acid, sulfuric acid, nitric acid, acetic acid, hydrofluoric acid, oxalic acid, and phosphoric acid, and mixed aqueous solutions of an acidic component and a salt selected from ferric chloride, ammonium fluoride, and potassium permanganate. The acidic component may also be a combination of a plurality of acidic components.
[0713] Examples of alkaline etching solutions include aqueous solutions of a single alkaline component selected from sodium hydroxide, potassium hydroxide, ammonia, organic amines, and salts of organic amines (tetramethylammonium hydroxide, etc.), and mixed aqueous solutions of an alkaline component and a salt (e.g., potassium permanganate). The alkaline component may also be a combination of a plurality of alkaline components.
[0714] It is also preferable to perform a rinsing process to remove the etching solution remaining on the substrate after the etching process and before moving to the next step. Water or the like can be used for the rinsing process.
[0715] After the etching process and / or the rinsing process, a drying process may be performed to remove excess liquid from the substrate.
[0716] 〔Pattern peeling process〕
[0717] The pattern peeling step in the second aspect can be performed by the same method as the pattern peeling step in the first aspect.
[0718] 〔Other processes〕
[0719] The method for producing a circuit wiring according to the present invention may include any steps (other steps) other than the above-mentioned steps. For example, the following steps may be mentioned, but the present invention is not limited to these steps.
[0720] Furthermore, examples of exposure steps, development steps, and other steps that can be applied to the method for manufacturing circuit wiring include steps described in paragraphs
[0035] to
[0051] of Japanese Patent Application Laid-Open No. 2006-23696.
[0721] <Process for reducing visible light reflectivity>
[0722] The method for producing a circuit wiring may include a step of performing a treatment to reduce the visible light reflectivity of a part or all of a conductive layer included in the substrate.
[0723] As a treatment for reducing the visible light reflectance, an oxidation treatment can be mentioned. When the substrate has a conductive layer containing copper, the visible light reflectance of the conductive layer can be reduced by subjecting the copper to oxidation treatment to convert it into copper oxide and blackening the conductive layer.
[0724] The process of reducing the visible light reflectance is described in paragraphs
[0017] to
[0025] of Japanese Patent Application Publication No. 2014-150118 and paragraphs
[0041] ,
[0042] ,
[0048] , and
[0058] of Japanese Patent Application Publication No. 2013-206315, and the contents described in these publications are incorporated into this specification.
[0725] <Step of Forming an Insulating Film, Step of Forming a New Conductive Layer on the Surface of the Insulating Film>
[0726] The method for manufacturing a circuit wiring preferably also includes a step of forming an insulating film on the surface of the circuit wiring and a step of forming a new conductive layer on the surface of the insulating film. Through the above steps, a second electrode pattern insulated from the first electrode pattern can be formed.
[0727] The step of forming the insulating film is not particularly limited, and a known method of forming a permanent film may be used. Alternatively, an insulating film having a desired pattern may be formed by photolithography using a photosensitive material having insulating properties.
[0728] The process of forming a new conductive layer on the insulating film is not particularly limited. For example, a new conductive layer having a desired pattern may be formed by photolithography using a photosensitive material having conductivity.
[0729] In the method for manufacturing circuit wiring, it is also preferred to use a substrate having a plurality of conductive layers on both surfaces of the substrate, and to form circuits on the conductive layers formed on the two surfaces of the substrate one after another or simultaneously. With this configuration, a circuit wiring for a touch panel having a first conductive pattern formed on one surface of the substrate and a second conductive pattern formed on the other surface can be formed. Furthermore, it is also preferred to form the circuit wiring for a touch panel having such a configuration from both surfaces of the substrate in a roll-to-roll manner.
[0730] 〔Purpose of circuit wiring〕
[0731] The circuit wiring manufactured by the manufacturing method of the circuit wiring can be applied to various devices. As a device having the circuit wiring manufactured by the above-mentioned manufacturing method, for example, an input device can be cited, preferably a touch panel, and more preferably an electrostatic capacitance touch panel. In addition, the above-mentioned input device can be applied to display devices such as organic FL display devices and liquid crystal display devices.
[0732] [Manufacturing method of printed wiring board]
[0733] The transfer film of the present invention can be used for the manufacture of a printed wiring board. The method for manufacturing a printed wiring board comprises a step of performing at least one selected from etching and plating on a substrate having the above-mentioned photoresist pattern. Here, in the etching or plating of the substrate, the developed photoresist pattern can be used as a mask, and the surface of the substrate can be etched or plated by a known method.
[0734] Furthermore, before the etching process or the plating process, a residual film removal process may be performed by resin etching using a chemical solution containing potassium permanganate or the like, resin ashing using plasma, or the like.
[0735] Examples of etching solutions used in the etching process include cupric chloride solutions, ferric chloride solutions, and alkaline etching solutions. Examples of plating include copper plating, solder plating, nickel plating, and gold plating.
[0736] After etching or plating, the photoresist pattern can be stripped with, for example, an aqueous solution that is more alkaline than the alkaline aqueous solution used for development. As the strongly alkaline aqueous solution, for example, a 1% to 10% by mass sodium hydroxide aqueous solution and a 1% to 10% by mass potassium hydroxide aqueous solution are used. In addition, as a stripping method, for example, an immersion method and a spraying method can be cited. In addition, the printed wiring board formed with the photoresist pattern can be a multilayer printed wiring board, and can also have a small-diameter through hole.
[0737] When plating a substrate having an insulating layer and a conductor layer formed on the insulating layer, it is necessary to remove the conductor layer except for the photoresist pattern. As a method for removing the conductor layer, for example, the following methods can be cited: lightly etching after peeling off the photoresist pattern; plating with solder after plating, peeling off the photoresist pattern, thereby covering the wiring part with solder, and then treating with an etching solution that can etch only the conductor layer that is not covered by solder.
[0738] Example
[0739] Below, examples are given to further specifically describe the embodiments of the present invention. The materials, usage, ratio, processing content and processing steps shown in the following examples can be appropriately changed as long as they do not depart from the purport of the embodiments of the present invention. Therefore, the scope of the embodiments of the present invention is not limited to the specific examples shown below.
[0740] <Preparation of Photosensitive Composition>
[0741] The components used to prepare the photosensitive composition are as follows.
[0742] 〔Polymer A〕
[0743] Alkali-soluble resin 1 having a crosslinking group: styrene (St) / methyl methacrylate (MMA) / methacrylic acid (MAA) / methacrylic acid-glycidyl methacrylate (GMA-MAA) = 47.7 / 1.3 / 19 / 32 (mass ratio), Mw: 20,000, acid value: 124 mgKOH / g, glass transition temperature: 76°C, solid content: 30% by mass, weight average molecular weight: 20,000
[0744] Alkali-soluble resin 2 having a crosslinking group: Styrene (St) / methyl methacrylate (MMA) / methacrylic acid (MAA) / methacrylic acid-glycidyl methacrylate (GMA-MAA) = 34 / 15 / 19 / 32 (mass ratio), Mw: 20,000, acid value: 124 mgKOH / g, glass transition temperature: 77°C, solid content: 30% by mass, weight average molecular weight: 20,000
[0745] Alkali-soluble resin 3 having a crosslinking group: Styrene (St) / methyl methacrylate (MMA) / methacrylic acid (MAA) / methacrylic acid-glycidyl methacrylate (GMA-MAA) = 22 / 27 / 19 / 32 (mass ratio), Mw: 20,000, acid value: 124 mgKOH / g, glass transition temperature: 78°C, solid content: 30% by mass, weight average molecular weight: 20,000
[0746] Moreover, "methacrylic acid-glycidyl methacrylate" means a structural unit obtained by reacting an epoxy group of glycidyl methacrylate with a carboxyl group of a structural unit derived from methacrylic acid.
[0747] 〔Polymerizable compounds〕
[0748] · BPE-500: Product name: "NK Ester BPE-500", ethoxylated bisphenol A dimethacrylate, average number of ethylene oxide chain repeats 10, manufactured by Shin-Nakamura Chemical Co., Ltd. · BPE-100: Product name: "NK Ester BPE-100", ethoxylated bisphenol A dimethacrylate, average number of ethylene oxide chain repeats 2.6, manufactured by Shin-Nakamura Chemical Co., Ltd.
[0749] ·M-270: Product name: "ARONIX M-270", polypropylene glycol diacrylate, manufactured by TOAGOSEI CO., LTD.
[0750] In addition, the above-mentioned BPE-500 and BPE-100 correspond to the polymerizable compound B1.
[0751] 〔Polymerization initiator〕
[0752] ·B-CIM: Product name: "B-CIM" (2-(2-chlorophenyl)-4,5-diphenylimidazole dimer, manufactured by KUROGANEKASEI Co., Ltd.
[0753] 〔Sensitizer〕
[0754] ·EAB-F: Product name: "EAB-F", 4,4'-bis(diethylamino)benzophenone, manufactured by Sanyo Trading Co., Ltd.
[0755] 〔Inhibitor〕
[0756] ・Phenothiazine (manufactured by FUJIFILM Wako Pure Chemical Corporation)
[0757] 〔Antioxidant〕
[0758] · Phenidone 1% MEK solution: a methyl ethyl ketone solution containing 1% by mass of phenidone, manufactured by Tokyo Chemical Industry Co., Ltd.
[0759] 〔Chain transfer agent〕
[0760] Compound A: N-phenylcarbamoylmethyl-N-carboxymethylaniline, manufactured by FUJIFILM Wako Pure Chemical Corporation
[0761] 〔pigment〕
[0762] ·LCV: Colorless crystal violet, manufactured by Tokyo Chemical Industry Co., Ltd., a pigment that develops color through free radicals
[0763] Malachite green: Malachite green oxalate (manufactured by FUJIFILM Wako Pure Chemical Corporation)
[0764] 〔Rust inhibitor〕
[0765] ·CBT-1: Product name: "CBT-1", carboxybenzotriazole, manufactured by Johoku Chemical Co., Ltd.
[0766] 〔Surfactant〕
[0767] ·F-552: Product name: "MEGAFACE F-552", manufactured by DIC Corporation
[0768] 〔Solvent〕
[0769] MMPGAc: 1-methoxy-2-propyl acetate
[0770] MEK: Methyl Ethyl Ketone
[0771] MFG: Propylene glycol monomethyl ether
[0772] The above components were mixed in the amounts (parts by mass) shown in Table 1 to prepare a photosensitive composition.
[0773] <Preparation of Intermediate Layer Forming Composition>
[0774] The components used to prepare the intermediate layer forming composition are as follows.
[0775] 〔Water-soluble resin〕
[0776] ·PVA: Polyvinyl alcohol
[0777] ·PVP: Polyvinylpyrrolidone
[0778] HPMC: Hydroxypropyl methylcellulose
[0779] 〔Surfactant〕
[0780] ·F-444: Product name: "MEGAFACE F-444", manufactured by DIC Corporation
[0781] 〔Solvent〕
[0782] Methanol
[0783] Pure water
[0784] The above components were mixed in the contents (parts by mass) shown in Table 1 to prepare a composition for forming an intermediate layer.
[0785] <Preparation of Thermoplastic Resin Layer-Forming Composition>
[0786] The components used to prepare the thermoplastic resin layer-forming composition are as follows.
[0787] 〔Thermoplastic resin〕
[0788] Alkali-soluble resin B1: benzyl methacrylate (BzMA) / methacrylic acid (MAA) / acrylic acid (AA) = 78 / 14.5 / 7.5 (mass ratio), Mw: 12,500, acid value: 187 mgKOH / g, glass transition temperature: 75°C, solid content: 30% by mass
[0789] 〔Polymerizable compounds〕
[0790] ·A-DCP: Product name: "NK Ester A-DCP", tricyclodecane dimethanol diacrylate, manufactured by Shin-Nakamura Chemical Co., Ltd.
[0791] 8UK-015A: Product name: "8UK-015A", UV curable urethane acrylate, manufactured by Taisei Fine Chemical Co., Ltd.
[0792] TO-2349: Product name: "ARONIX TO-2349", manufactured by TOAGOSEI CO., LTD.
[0793] 〔Inhibitor〕
[0794] · Phenothiazine (manufactured by FUJIFILM Wako Pure Chemical Corporation)
[0795] 〔Rust inhibitor〕
[0796] ·CBT-1: Product name: "CBT-1", carboxybenzotriazole, manufactured by Johoku Chemical Co., Ltd.
[0797] 〔Surfactant〕
[0798] ·F-552: Product name: "MEGAFACE F-552", manufactured by DIC Corporation
[0799] 〔Solvent〕
[0800] MEK: Methyl Ethyl Ketone
[0801] [Table 1]
[0802]
[0803] In Table 1, "B / A" means the ratio of the total mass of the polymerizable compound B1 to the total mass of the polymer A.
[0804] <Preparation of temporary support>
[0805] Temporary supports 1 to 6 as biaxially stretched PET films shown in Table 2 were prepared.
[0806] For each temporary support, thickness, thermal deformation rate, haze, surface energy, surface roughness Rmax, total number of particles with a diameter of 5 μm or more and aggregates with a diameter of 5 μm or more, and total area ratio of optical abnormal regions were measured. The measurement method is as follows.
[0807] (thickness)
[0808] The value was calculated as the average value of five arbitrary points measured by cross-section observation using SEM.
[0809] (Thermal deformation rate)
[0810] On the main surface of the temporary support, a direction parallel to one of two sets of sides facing each other is referred to as direction A, and a direction perpendicular to direction A is referred to as direction B.
[0811] A test piece cut to a length of 30 mm in the A direction and 4 mm in the B direction and a test piece cut to a length of 30 mm in the B direction and 4 mm in the A direction were prepared.
[0812] The following measurements were performed using two test pieces.
[0813] As a measuring device, a thermal expansion coefficient measuring device (product name: "TMA450EM", manufactured by TA Instruments) was used.
[0814] The measurement conditions are as follows.
[0815] Measurement mode: Stretch mode
[0816] Distance between grippers: 16mm
[0817] Set load: from 0.05N to 0.48N at 6.00N / min.
[0818] Each test piece was heated from 25° C. to 100° C. at a heating rate of 20° C. / min, and the elongation of each test piece was measured five times, and the average value was calculated.
[0819] The larger average value of the elongation of the two test pieces was adopted as the heat deformation rate.
[0820] (Haze)
[0821] The haze meter was used to measure in accordance with JIS K7136:2000.
[0822] (Surface roughness Rmax)
[0823] The temporary support was peeled off from the transfer film. The surface profile of the transfer layer side surface of the temporary support was obtained. As the measurement / analysis software, Microscope Application of MetroPro ver8.3.2 was used. Next, the Surface Map screen was displayed using the measurement / analysis software, and histogram data was obtained in the Surface Map screen. The surface roughness Rmax was obtained from the obtained histogram data.
[0824] (Total number of particles with a diameter of 5 μm or more and aggregates with a diameter of 5 μm or more)
[0825] The temporary support was observed with a polarizing microscope (a simple polarizing microscope with "U-POT" filter and "U-AN360" filter inserted into the product name: "BX60", objective lens 10x, manufactured by Olympus Corporation), and the portion where polarization disorder occurred was determined as a foreign matter (particle or agglomerate). The identified foreign matter was observed with an incident laser microscope (product name: "Confocal Laser Microscope VL2000D", manufactured by Lasertec), and the total area ratio of the optical abnormal area described later was measured. In addition, the diameter of the foreign matter was measured with an optical microscope (product name: "BX60", objective lens 100x, manufactured by Olympus Corporation), and the observation area 1mm was measured. 2 The number of foreign particles with a diameter of 5 μm or more contained in the sample.
[0826] (Total area ratio of optical abnormal area)
[0827] A polarizing filter (OLS4000-QWP) was inserted into the upper part of the objective lens of an incident laser microscope (OLS-4100 manufactured by Olympus). Next, a temporary support cut to 30 mm × 30 mm was fixed horizontally by suction on the platform of the laser microscope using a porous adsorption plate (65F-HG manufactured by UNIVERSAL GIKEN CO., ITD.) and a vacuum pump. The fixed temporary support was observed with a laser light intensity of 60 (laser wavelength of 405 nm) at 50 times the objective lens. At this time, the central 2 μm area in the thickness direction of the temporary support was defined as the measurement area, and the measurement area of 259 μm × 260 μm was measured at 200 measurement locations.
[0828] The light intensity difference between the pixel with the maximum light intensity and the pixel with the minimum light intensity in the measured image is divided into 4096 gray levels (the value of the maximum light intensity is 4095 and the value of the minimum light intensity is 0). A histogram is produced that shows the light intensity distribution of the pixels in the image in a graphical form (horizontal axis: gray level of light intensity (minimum value 0, maximum value 4095), vertical axis: number of pixels). The gray level after adding 400 gray levels to the larger of the two base values of the produced histogram is used as the threshold, and the measured image is binarized. The area of the pixels with light intensity greater than the threshold is totaled, and the total area is used as the total area of the optical abnormal area. The ratio of the total area of the optical abnormal area to the measured area is calculated.
[0829] <Production of transfer film>
[0830] [Example 1]
[0831] Using a slit nozzle, an intermediate layer forming composition was applied to the temporary support 1 in such a manner that the thickness after drying became the thickness of the intermediate layer described in Table 1. The coating film of the intermediate layer forming composition was dried at 90° C. for 120 seconds to form an intermediate layer. Using a slit nozzle, a photosensitive composition was applied to the intermediate layer in such a manner that the thickness after drying became the thickness of the photosensitive layer described in Table 1. The coating film of the photosensitive composition was dried at 80° C. for 120 seconds to form a photosensitive layer. That is, an intermediate layer and a photosensitive layer were formed as a transfer layer 1 on the temporary support 1. Thus, a transfer film having a temporary support 1, an intermediate layer, and a photosensitive layer in sequence was obtained.
[0832] The surface free energy of the transfer layer 1 on the side facing the temporary support 1 is 60.1 mJ / m 2 .
[0833] The content of water in the transfer layer 1 was 0.1% by mass based on the total amount of the transfer layer 1 .
[0834] The content of iron atoms in the transfer layer 1 was 0.01 ppm based on the total amount of the transfer layer 1 .
[0835] The content of water in the photosensitive layer was 0.1% by mass based on the total amount of the photosensitive layer.
[0836] The content of iron atoms in the photosensitive layer was 0.01 ppm based on the total amount of the photosensitive layer.
[0837] [Example 2 to Example 5, Comparative Example 1]
[0838] A transfer film was obtained by the same method as in Example 1 except that the temporary support 1 was changed to temporary supports 2 to 6 .
[0839] The surface free energy of the transfer layer 1 on the sides facing the temporary supports 2 to 6 was 60.1 mJ / m 2 .
[0840] [Example 6]
[0841] Using a slit nozzle, a composition for forming an intermediate layer was applied to the temporary support 2 in such a manner that the thickness after drying became the thickness of the intermediate layer described in Table 1. The coating film of the composition for forming the intermediate layer was dried at 90°C for 120 seconds to form an intermediate layer. Using a slit nozzle, a composition for a thermoplastic resin layer was applied to the intermediate layer in such a manner that the thickness after drying became the thickness of the thermoplastic resin layer described in Table 1. The coating film of the composition for a thermoplastic resin layer was dried at 100°C for 120 seconds to form a thermoplastic resin layer. Using a slit nozzle, a photosensitive composition was formed on the thermoplastic resin layer in such a manner that the thickness after drying became the thickness of the photosensitive layer described in Table 1. The coating film of the photosensitive composition was dried at 80°C for 120 seconds to form a photosensitive layer. That is, a thermoplastic resin layer, an intermediate layer and a photosensitive layer were formed as a transfer layer 2 on the temporary support 2. Thus, a transfer film having a temporary support 2, a thermoplastic resin layer, an intermediate layer and a photosensitive layer in sequence was obtained.
[0842] The surface free energy of the transfer layer 2 on the side facing the temporary support 2 is 60.1 mJ / m 2 .
[0843] The content of water in the transfer layer 2 was 0.1% by mass based on the total amount of the transfer layer 2 .
[0844] The content of iron atoms in the transfer layer 2 was 0.01 ppm based on the total amount of the transfer layer 2 .
[0845] The content of water in the photosensitive layer was 0.1% by mass based on the total amount of the photosensitive layer.
[0846] The content of iron atoms in the photosensitive layer was 0.01 ppm based on the total amount of the photosensitive layer.
[0847] The transfer films obtained in Examples and Comparative Examples were used to evaluate substrate deformability, reticulation, and patterning properties. The evaluation results are shown in Tables 2 and 3.
[0848] [Example 7 to Example 15]
[0849] Except having changed the transfer layer and the temporary support body into the content described in Table 2 and Table 3, it carried out similarly to Example 1, and obtained the transfer film.
[0850] In Example 7, the surface free energy of the transfer layer 1 on the side facing the temporary support 6 is 60.1 mJ / m 2 .
[0851] In Examples 8 and 12, the surface free energy of the transfer layer 3 on the side facing each temporary support was 60.1 mJ / m 2 .
[0852] In Examples 9 and 13, the surface free energy of the transfer layer 4 on the side facing each temporary support was 60.1 mJ / m 2 .
[0853] In Examples 10 and 14, the surface free energy of the transfer layer 5 on the side facing each temporary support was 60.1 mJ / m 2 .
[0854] In Examples 1 and 15, the surface free energy of the transfer layer 6 on the side facing each temporary support is 60.1 mJ / m 2 .
[0855] The content of water in the transfer layers 3 to 6 was 0.1% by mass based on the total amount of each of the transfer layers 3 to 6 .
[0856] The content of iron atoms in the transfer layers 3 to 6 was 0.01 ppm based on the total amount of each of the transfer layers 3 to 6 .
[0857] The content of water in the photosensitive layers of the transfer layers 3 to 6 was 0.1% by mass based on the total amount of the photosensitive layers.
[0858] The content of iron atoms in the photosensitive layers of transfer layers 3 to 6 was 0.01 ppm based on the total amount of the photosensitive layers.
[0859] <Substrate Deformability>
[0860] A transfer film and a substrate (product name: "Meta Royal", manufactured by Toray Advanced Materials Korea) were laminated using a vacuum laminator (product name: "MVR-250T", manufactured by MCK Co., Ltd.) in such a way that the photosensitive layer of the transfer film was in contact with the substrate. In addition, the transfer film was laminated to both surfaces of the substrate. The lamination process was carried out under the conditions of a conveying speed of 1 m / min, a vacuum degree of 50 Pa, and a lamination temperature of 100°C. A laminated body was obtained in which a temporary support, a transfer layer (intermediate layer / photosensitive layer), a substrate, a transfer layer (photosensitive layer / intermediate layer), and a temporary support were laminated in this order.
[0861] In the obtained laminate, one temporary support was peeled off, and the laminate after peeling was placed with the surface from which the temporary support was peeled off as the upper surface, and the deformation amount of the substrate was measured.
[0862] The distance between the center of the substrate and the end of the substrate in the vertical direction was defined as the deformation amount of the substrate. The evaluation criteria were as follows.
[0863] A: The deformation is less than 1 cm.
[0864] B: The deformation amount is more than 1 cm and less than 3 cm.
[0865] C: The deformation amount is more than 3 cm and less than 5 cm.
[0866] D: The deformation exceeds 5 cm.
[0867] <Reticulation>
[0868] In the same manner as in the evaluation of substrate deformability, a laminated body in which a temporary support, a transfer layer (intermediate layer / photosensitive layer), a substrate, a transfer layer (photosensitive layer / intermediate layer), and a temporary support were laminated in this order was obtained.
[0869] One temporary support was peeled off from the obtained laminate under an environment of a temperature of 23 degrees and a humidity of 50%. The surface of the transfer layer after peeling was visually observed to check whether wrinkles (wrinkles) were generated. The evaluation criteria were as follows.
[0870] A: No moire occurs.
[0871] B: Screen marks are generated.
[0872] <Patternability>
[0873] A transfer film and a substrate (product name: "Meta Royal", manufactured by Toray Advanced Materials Korea) were laminated using a vacuum laminator (product name: "MVR-250T", manufactured by MCK Co., Ltd.) in such a way that the photosensitive layer of the transfer film was in contact with the substrate. In addition, the transfer film was laminated to one surface of the substrate. The lamination process was carried out under the conditions of a conveying speed of 1 m / min, a vacuum degree of 50 Pa, and a lamination temperature of 100°C. A laminated body in which a temporary support, a transfer layer (intermediate layer / photosensitive layer), and a substrate were laminated in this order was obtained.
[0874] In the obtained laminate, the temporary support was peeled off (peeling step). After the peeling step, the transfer layer was exposed to light at an exposure amount of 50 mJ / cm 2 Ultraviolet rays were irradiated (exposure process). The photomask used in the exposure had a line and space pattern with a ratio of the width of the transmission area to the light-shielding area (duty ratio) of 1:1 and a line width (and gap width) of 15 μm. After the exposure process, spray development was performed for 30 seconds using a 1.0 mass % sodium carbonate aqueous solution at a liquid temperature of 25°C (development process). After the development process, the formed pattern was observed with an optical microscope to confirm the presence or absence of pattern defects (e.g., broken lines, omissions, defects, etc.). The evaluation criteria are as follows.
[0875] A: No pattern defects.
[0876] B: There are pattern defects.
[0877] The evaluation results are shown in Tables 2 and 3.
[0878] [Table 2]
[0879]
[0880] [Table 3]
[0881]
[0882] As shown in Tables 2 and 3, in Examples 1 to 15, since the temporary support and the transfer layer disposed on the temporary support were included, the thermal deformation rate of the temporary support was 1.0% or less, and thus deformation of the substrate used in the transfer process could be suppressed.
[0883] On the other hand, in Comparative Example 1, it was found that the thermal deformation rate of the temporary support body exceeded 1.0%, and the substrate was deformed.
[0884] In Example 2, it is found that the patterning property is superior to that in Example 3 because the surface roughness Rmax of the transfer layer side surface of the temporary support is 0.5 μm or less.
[0885] <Example 101: Production of Flexible Printed Wiring Board>
[0886] A polyimide substrate with a copper layer was prepared by providing a copper layer with a thickness of 300 nm on both surfaces of a polyimide substrate with a thickness of 25 μm (Kapton 100H, manufactured by TORAY INDUST RIES, INC.) by a deposition method.
[0887] <Exposure method 1>
[0888] The transfer film of Example 1 was laminated on both surfaces of the polyimide substrate with copper layers under lamination conditions of roll temperature 100° C., linear pressure 1.0 MPa, and linear speed 1.0 m / min so that the copper layer and the photosensitive layer were in contact, thereby producing a laminate for evaluation.
[0889] Next, the temporary support bodies on both sides were peeled off in a direction of 180°.
[0890] Next, a photomask having a pattern of a prescribed line width (μm) / gap width (μm) was used to expose both surfaces simultaneously in such a way that the intermediate layer was in contact with the mask. A high-pressure mercury lamp with i-ray (365nm) as the main exposure wavelength was used for exposure. The exposure amount was arbitrarily set so that the top shape of each pattern was consistent with the mask opening. The two surfaces were spray-developed with a 1% by mass sodium carbonate aqueous solution at a liquid temperature of 30°C and washed with water, thereby obtaining a laminate having a prescribed pattern formed on the copper layer of both surfaces.
[0891] The laminate was subjected to acid degreasing, water washing and sulfuric acid immersion in sequence, and then plated with a copper sulfate solution at 1 A / dm 2 The copper plating treatment was carried out under the conditions of 50°C until the plating thickness reached 15 μm. After washing and drying, the photoresist was stripped using a 3.0 mass % sodium hydroxide aqueous solution at 50°C, and the seed layer was removed using an etching solution (an aqueous solution containing 0.1 mass % sulfuric acid and 0.1 mass % hydrogen peroxide, 28°C), and then washed with water to produce a flexible printed wiring board. It was confirmed that the manufactured flexible printed wiring board operated normally.
[0892] <Exposure method 2>
[0893] The transfer film of Example 1 was laminated on both surfaces of a polyimide substrate with copper layers under lamination conditions of roll temperature 100° C., linear pressure 1.0 MPa, and linear speed 1.0 m / min so that the copper layer and the photosensitive layer were in contact, thereby producing a laminate for evaluation.
[0894] Next, one surface of the temporary support was peeled off in a direction of 180°, and the peeled surface was exposed.
[0895] For exposure, a projection exposure machine with a high-pressure mercury lamp was used and i-ray (365 nm) was used for reduced projection exposure through a mask. As a mask, a template with a pattern of a predetermined line width (μm) / gap width (μm) was used. In addition, the exposure amount was arbitrarily set so that the top shape of each pattern matched the mask opening.
[0896] Next, the temporary support of the transfer film on the side opposite to the exposed surface was peeled off in a direction of 180°, and the peeled surface was exposed under the same conditions as those of the first exposed surface.
[0897] Both surfaces were shower-developed with a 1 mass % sodium carbonate aqueous solution at a liquid temperature of 30° C., and then washed with water to obtain a laminated body having a predetermined pattern formed on the copper layers on both surfaces.
[0898] The laminate was subjected to acid degreasing, water washing and sulfuric acid immersion in sequence, and then plated with a copper sulfate solution at 1 A / dm 2 The copper plating treatment was carried out under the conditions of 50°C until the plating thickness reached 15 μm. After washing and drying, the photoresist was stripped using a 3.0 mass % sodium hydroxide aqueous solution at 50°C, and the seed layer was removed using an etching solution (an aqueous solution containing 0.1 mass % sulfuric acid and 0.1 mass % hydrogen peroxide, 28°C), and then washed with water to produce a flexible printed wiring board. It was confirmed that the manufactured flexible printed wiring board operated normally.
[0899] [Examples 102 to 115]
[0900] Flexible printed wiring boards were produced in the same manner as in Example 101 except that the transfer films of Examples 2 to 15 were used. It was confirmed that the flexible printed wiring boards produced by either the exposure method 1 or the exposure method 2 also operated normally.
[0901] In addition, the entire contents disclosed in Japanese Patent Application No. 2022-106641 filed on June 30, 2022 and Japanese Patent Application No. 2023-000740 filed on January 5, 2023 are incorporated into this specification by reference. In addition, all documents, patent applications, and technical standards described in this specification are incorporated into this specification by reference to the same extent as if each document, patent application, and technical standard was specifically and individually described as being incorporated by reference.
Claims
1. A transfer film comprising a temporary support and a transfer layer disposed on the temporary support, The thermal deformation rate of the temporary support is 1.0% or less.
2. The transfer film according to claim 1, wherein The surface free energy of the transfer layer on the side facing the temporary support is 68.0 mJ / m 2 the following.
3. The transfer film according to claim 1 or 2, wherein The transfer layer is in contact with the surface of the temporary support, The surface roughness Rmax of the transfer layer side surface of the temporary support is 0.5 μm or less.
4. The transfer film according to claim 1 or 2, wherein The transfer layer includes a photosensitive layer.
5. The transfer film according to claim 4, wherein The transfer layer includes an intermediate layer between the temporary support and the photosensitive layer.
6. The transfer film according to claim 5, wherein The transfer layer includes a thermoplastic resin layer between the temporary support and the intermediate layer.
7. The transfer film according to claim 1 or 2, wherein: The temporary support has a haze of greater than 2.0%.
8. The transfer film according to claim 1 or 2, wherein The total number of particles with a diameter of 5 μm or more and aggregates with a diameter of 5 μm or more contained in the temporary support is more than 30 / mm 2 .
9. The transfer film according to claim 1 or 2, wherein: The temporary support comprises a 13.5 mm 2 The area in which the total area ratio of the optical abnormal area during observation is greater than 300 ppm.
10. The transfer film according to claim 1 or 2, wherein The temporary support has a thickness of 25 μm or more.
11. The transfer film according to claim 4, wherein The photosensitive layer includes an alkali-soluble resin having an acid value of 80 mgKOH / g to 250 mgKOH / g.
12. The transfer film according to claim 4, wherein The photosensitive layer contains an alkali-soluble resin having a crosslinkable group.
13. The transfer film according to claim 4, wherein The photosensitive layer includes an alkali-soluble resin having a content of a structural unit derived from a (meth)acrylate ester in a mass ratio of 0.3 to 2.5 with respect to a total content of a structural unit derived from styrene and a structural unit derived from a styrene derivative.
14. The transfer film according to claim 1 or 2, wherein: The water content of the transfer layer is 0.1% by mass or more based on the total amount of the transfer layer.
15. The transfer film according to claim 4, wherein The water content of the photosensitive layer is 0.1% by mass or more based on the total amount of the photosensitive layer.
16. The transfer film according to claim 1 or 2, wherein: The content of iron atoms in the transfer layer is 0.01 ppm to 10.0 ppm on a mass basis relative to the total amount of the transfer layer.
17. The transfer film according to claim 4, wherein: The content of iron atoms in the photosensitive layer is 0.01 ppm to 10.0 ppm on a mass basis relative to the total amount of the photosensitive layer.
18. A method for forming a pattern, comprising the following steps: preparing a transfer film including a temporary support and a transfer layer disposed on the temporary support; The transfer film and the substrate are bonded together in such a manner that a surface of the transfer film on the side opposite to the surface of the temporary support is in contact with the substrate; peeling off the temporary support to obtain a laminated body; exposing the laminate in a pattern; and developing the exposed laminate to form a pattern, The thermal deformation rate of the temporary support is 1.0% or less.
19. A method for manufacturing a circuit wiring, comprising the following steps: preparing a transfer film including a temporary support and a transfer layer disposed on the temporary support; The transfer film and the substrate are bonded together in such a manner that a surface of the transfer film on the side opposite to the surface of the temporary support is in contact with the substrate; peeling off the temporary support to obtain a laminated body; exposing the laminate in a pattern; developing the exposed laminate to form a pattern; performing a plating process on a region of the substrate where the pattern is not arranged; and Peel off the pattern, The thermal deformation rate of the temporary support is 1.0% or less.
Citation Information
Patent Citations
Method and device for spraying dispersion system
JP1982053266A
Photosensitive transfer material and image forming method
JP1993072724A
Lithographic printing original plate
JP2004239942A
Multicolor image forming material
JP2005007765A
Colored photosensitive resin composition, coating film of colored photosensitive resin composition, photosensitive resin transfer material, method for forming photosensitive resin layer, color filter, method for manufacturing color filter, and liquid crystal display
JP2006023696A